Battery cell, battery device, power consuming device, and energy storage device
Patent Information
- Application Number
- CN202610778770.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2026-04-16
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-02
AI Technical Summary
[0140] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application.
Smart Images

Figure CN122314858B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority to PCT patent application PCT / CN2026 / 090974, filed on April 16, 2026, entitled “Battery cell, battery device, power consumption device and energy storage device”, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This application relates to the field of battery technology, and in particular to a battery cell, battery device, power supply device, and energy storage device. Background Technology
[0004] Energy conservation and emission reduction are crucial for sustainable social development. Rechargeable batteries, with their ability to store and release energy as needed, are widely used in various electrical devices and energy storage systems, and are an important component in promoting energy transition and sustainable development. For the new energy industry, battery technology is a critical factor in its development. How to balance battery manufacturing costs, energy density, and cycle life is a pressing issue that needs to be addressed in this field. Summary of the Invention
[0005] This application aims to at least solve one of the technical problems existing in the background art. To this end, one object of this application is to provide a battery cell, battery device, power consumption device, and energy storage device that improves the cycle life of the battery cell while taking into account battery cost and energy density.
[0006] The first aspect of this application provides a battery cell, including a casing, electrode terminals, an electrode assembly, and an electrolyte. The casing forms a cavity inside and has a through-hole communicating with the inside and outside of the cavity. The electrode terminals include a first portion and a second portion. The first portion is entirely located within the cavity, and the second portion extends through the through-hole and partially outside the cavity. The first and second portions are integrally formed. The electrode assembly and electrolyte are disposed within the cavity. The electrode assembly includes an electrode sheet and a tab, with the tab directly connected to the first portion. The electrode sheet includes a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The positive active material layer includes a positive active material, which comprises lithium-containing transition metal oxide particles and a lithium-containing... Lithium transition metal phosphate particles; lithium transition metal oxide particles include nickel, cobalt, and M elements, where M elements include manganese and / or aluminum; lithium transition metal phosphate particles include iron and manganese; based on the total molar number of manganese and iron elements in the lithium transition metal phosphate particles, the molar number of manganese is 40%-75%; in the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium transition metal phosphate particles is 100nm-300nm, and the Dn90 of the lithium transition metal phosphate particles is 250nm-500nm, where Dn50 and Dn90 refer to the particle size corresponding to 50% and 90% of the cumulative particle number distribution curve.
[0007] The positive electrode active material includes lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles. The lithium-containing transition metal oxide particles include nickel, cobalt, and M elements, with M elements including manganese and / or aluminum. The lithium-containing transition metal phosphate particles include iron and manganese. The molar percentage of manganese in the lithium-containing transition metal phosphate particles is 40%-75%, and the Dn50 of the lithium-containing transition metal phosphate particles is 100nm-300nm, and the Dn90 is 250nm-500nm. When the tabs on the electrode assembly are directly connected to the first part of the electrode terminal, it is beneficial to improve the cycle stability of the hybrid system battery cell.
[0008] Using a mixture of lithium transition metal phosphate particles and lithium transition metal oxide particles as the positive electrode active material helps to balance the manufacturing cost and energy density of the battery cell. To fully utilize the specific capacity of the lithium transition metal oxide particles and improve the energy density of the battery cell, the charging cutoff voltage of the battery cell needs to be set to around 4.25V. The main discharge voltage range of the lithium transition metal oxide particles is significantly higher than that of the lithium transition metal phosphate particles. This means that the lithium transition metal phosphate particles mainly bear the main lithium-ion supply in the low-voltage range, while the lithium transition metal oxide particles mainly bear the main lithium-ion supply in the high-voltage range. This results in both materials experiencing an equivalent rate load much higher than the apparent rate in their corresponding operating ranges, i.e., load shunting. Therefore, even at low rates of charge and discharge, the load shunting phenomenon in the hybrid battery cell still causes rapid lithium-ion insertion / extraction within the positive electrode active material. The structural stability of the lithium transition metal oxide is poor, and it is easily affected by load shunting during cycling, which is significantly detrimental to its structural integrity. Sustained current overload can easily trigger irreversible phase transitions in lithium-containing transition metal oxide particles. Simultaneously, the rapid and non-uniform insertion / extraction of lithium ions at high current densities leads to a severe mismatch between the surface and bulk lattice parameters of the lithium-containing transition metal oxide particles, generating enormous internal stress within the particles. This triggers the initiation and propagation of grain boundary microcracks, ultimately causing particle breakage and surface structure collapse, resulting in decreased cycle stability of the hybrid battery cells. Therefore, reducing the current loaded by lithium-containing transition metal oxides has become crucial for improving the cycle stability of hybrid systems.
[0009] Compared to lithium iron phosphate, lithium transition metal phosphate particles, which contain both manganese and iron, can mitigate the voltage mismatch between the two materials by utilizing two voltage platforms. However, when the molar proportion of manganese in lithium transition metal phosphate particles is less than 40%, the capacity of these particles in the high-voltage range is reduced, hindering their compatibility with lithium transition metal oxide particles at high voltages and failing to effectively alleviate load shunting. While a molar proportion of manganese in lithium transition metal phosphate particles greater than 75% improves voltage platform compatibility, significant manganese ion dissolution still negatively impacts the cycle stability of the hybrid battery cells.
[0010] like Figure 1 As shown, controlling the molar proportion of manganese in lithium transition metal phosphate particles to 40%-75% results in a high degree of matching between manganese and lithium transition metal oxide particles under high voltage, which can reduce the impact of high voltage ( Figure 1 The discharge voltage range under medium and high voltage conditions is used to control the current of lithium transition metal oxide loads, while also controlling the degree of manganese ion dissolution within a reasonable range.
[0011] However, lithium-containing transition metal phosphate particles have low electronic conductivity and lithium-ion diffusion coefficient, resulting in poor intrinsic kinetic performance. Furthermore, when the molar proportion of manganese is 40%-75%, manganese ions will cause significant distortion, leading to the distortion of lithium-ion diffusion channels and further reducing the kinetic performance of lithium-containing transition metal phosphate particles.
[0012] During the charging and discharging process of a hybrid battery cell, lithium-containing transition metal phosphate particles with slow lithium-ion diffusion cannot complete charge transfer and lithium-ion intercalation / deintercalation in time. This causes the charging and discharging current to concentrate on lithium-containing transition metal oxide particles with better kinetics. As a result, lithium-containing transition metal phosphate particles still cannot effectively share the current, causing lithium-containing transition metal oxide particles to bear a high rate of current density even at a higher voltage than 3.7V.
[0013] By employing lithium transition metal phosphate particles containing iron and manganese, and controlling the molar ratio of manganese in the lithium transition metal phosphate particles to be greater than 40%-75%, and simultaneously matching the particles with a Dn50 of 100nm-300nm and a Dn90 of 250nm-500nm, the kinetic performance of the lithium transition metal phosphate particles and the voltage plateau matching with the lithium transition metal oxide particles can be balanced, thereby alleviating the load shunting phenomenon and improving the cycle stability of the hybrid battery system.
[0014] It is worth mentioning that the applicant discovered that the content of small particles in the positive electrode active material layer has a crucial impact on alleviating the load shunting phenomenon. As shown in Table 2, when the Dn50 of the lithium transition metal phosphate particles is 100nm-300nm but the Dn90 is greater than 500nm, it means that the lithium transition metal phosphate particles still contain a lot of large particles with insufficient kinetic performance. Most of the charge and discharge current still tends to concentrate in the lithium transition metal oxide particles with better kinetics, and cannot effectively alleviate the load shunting phenomenon.
[0015] However, small-sized lithium-containing transition metal phosphate particles have a large specific surface area, which can easily exacerbate the dissolution of manganese ions under high-temperature conditions. The manganese ions further dissolve in the electrolyte and are reduced and precipitated at the negative electrode, which can easily damage the solid electrolyte interphase (SEI) membrane. As a result, more active lithium is consumed during the SEI membrane repair process, which has an adverse effect on the cycle stability of the hybrid battery cells.
[0016] In this embodiment, the tabs on the electrode assembly are directly connected to the first part of the electrode terminal. Combined with the above-mentioned hybrid system, the impedance and heat generation at the tabs are reduced, the heat at the maximum heat generation point of the battery cell is reduced, the temperature distribution uniformity of the positive electrode active material layer is improved, the temperature rise of the positive electrode sheet is reduced, thereby reducing the probability of manganese ion dissolution of lithium transition metal phosphate particles, reducing the damage of manganese ions to the SEI film, reducing the consumption of active lithium ions, and improving the cycle stability of the hybrid system battery cell.
[0017] In any embodiment, based on the total number of moles of manganese and iron in the lithium-containing transition metal phosphate particles, the molar percentage of manganese is 45%-75%.
[0018] The molar ratio of manganese in lithium transition metal phosphate particles is within a reasonable range, which helps to reduce the dissolution of manganese ions, reduce the probability of manganese ions being reduced and precipitated at the negative electrode and causing damage to the SEI film, reduce the consumption of active lithium ions, and improve the cycle stability of the hybrid system battery cells.
[0019] In any embodiment, based on the total number of moles of manganese and iron in the lithium-containing transition metal phosphate particles, the molar percentage of manganese is 50%-70%.
[0020] The molar proportion of manganese in lithium transition metal phosphate particles is within a reasonable range, which is beneficial to improving the plateau voltage contributed by manganese, improving the matching degree between its voltage plateau and that of lithium transition metal oxide particles, alleviating the load shunting phenomenon caused by the step charging and discharging of the two types of materials, and improving the cycle stability of the hybrid system battery cells.
[0021] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn50 of the lithium transition metal phosphate particles is 100nm-250nm.
[0022] In the cross-section along the thickness direction of the positive electrode active material layer, the Dn50 of the lithium transition metal phosphate particles is within a reasonable range. Further reducing the particle size of the lithium transition metal phosphate particles is beneficial to reducing the lithium-ion transport path, improving the kinetic performance of the lithium transition metal phosphate particles, reducing the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reducing the probability of lithium transition metal oxide particles breaking and surface structure collapse due to current overload, and improving the cycle stability of the hybrid battery cell.
[0023] In any embodiment, in the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn90 of the lithium transition metal phosphate particles is 260nm-400nm.
[0024] In the cross-section along the thickness direction of the positive electrode active material layer, the Dn90 of the lithium transition metal phosphate particles is within a reasonable range, which can further balance the lithium ion transport path and the specific surface area of the lithium transition metal phosphate particles. This is beneficial to improving the kinetic performance of the lithium transition metal phosphate particles, reducing the degree of mismatch between the kinetic performance of the two types of materials in the hybrid battery cell, and reducing the probability of manganese ion dissolution of small-diameter lithium transition metal phosphate particles at high temperatures, thus comprehensively improving the cycle stability of the hybrid battery cell.
[0025] In any embodiment, in the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn10 of the lithium transition metal phosphate particles is 70nm-130nm, where Dn10 refers to the particle size corresponding to the cumulative number of particles being 10% in the cumulative distribution curve of particle number.
[0026] In the cross-section along the thickness direction of the positive electrode active material layer, the Dn10 of the lithium transition metal phosphate particles is within a reasonable range, which is beneficial to reduce the specific surface area of the lithium transition metal phosphate particles, reduce the probability of manganese ion dissolution of the lithium transition metal phosphate particles at high temperature, reduce the damage of manganese ions to the SEI film, reduce the consumption of active lithium ions, and improve the cycle stability of the hybrid system battery cell.
[0027] In any embodiment, the electrolyte includes a first component, which includes one or more of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethanesulfonyl)imide.
[0028] In any embodiment, the mass percentage of the first component is 0.05%-7% based on the total mass of the electrolyte.
[0029] Because the overall particle size of the lithium transition metal phosphate particles in this embodiment is relatively small, moisture is easily retained inside the battery during the cell manufacturing process. During the cycling process of the battery cell, this moisture easily reacts with conventional lithium-containing electrolyte salts such as lithium hexafluorophosphate in the electrolyte to generate highly corrosive hydrofluoric acid. Hydrofluoric acid easily damages the structure of the lithium transition metal oxide particles, causing transition metal ions to dissolve in the electrolyte and be reduced and precipitated at the negative electrode. Studies have shown that the transition metal deposited on the negative electrode acts as a catalyst, catalyzing the decomposition of the solid electrolyte interphase (SEI) film, causing more active lithium to be consumed during the SEI film repair process, which is detrimental to improving the cycle stability of the hybrid system battery cell.
[0030] The embodiments of this application further incorporate a certain amount of the aforementioned first component, which has excellent thermal stability and is not easily hydrolyzed. It can partially replace the mass ratio of conventional lithium-containing electrolyte salts (such as lithium hexafluorophosphate), which helps to reduce the generation of hydrofluoric acid, reduce the damage of the SEI film to the transition metal ions dissolved from the lithium transition metal oxide particles, reduce the loss of active lithium caused by rebuilding the SEI film, and improve the cycle stability of the hybrid system battery cells.
[0031] In any embodiment, the mass percentage of the first component is 0.5%-5% based on the total mass of the electrolyte.
[0032] A reasonable mass ratio of the first component in the electrolyte helps to reduce the mass ratio of conventional lithium-containing electrolyte salts (such as lithium hexafluorophosphate), reduce the generation of hydrofluoric acid, reduce its damage to the particle structure of lithium-containing transition metal oxides, and improve the cycle stability of the battery cells in the hybrid system.
[0033] In any embodiment, the mass percentage of the first component is 2%-5% based on the total mass of the electrolyte.
[0034] A reasonable mass ratio of the first component in the electrolyte helps to further reduce the mass ratio of conventional lithium-containing electrolyte salts (such as lithium hexafluorophosphate), reduce the generation of hydrofluoric acid, reduce its damage to the particle structure of lithium-containing transition metal oxides, and improve the cycle stability of the hybrid system battery cells.
[0035] In any embodiment, the first component includes one or more of lithium bis(fluorosulfonyl)imide and lithium difluorophosphate.
[0036] The first component includes one or more of lithium bis(fluorosulfonyl)imide and lithium difluorophosphate, which helps to reduce the formation of hydrofluoric acid and reduce its damage to the structure of lithium-containing transition metal oxide particles. At the same time, it forms a dense and stable CEI film (positive electrode electrolyte interface film), improves the chemical stability of the CEI film, further blocks the dissolution of transition metal ions in the positive electrode active material, and improves the cycle stability of the hybrid system battery cells.
[0037] In any embodiment, the mass percentage of lithium bis(fluorosulfonyl)imide is 0.05%-2% based on the total mass of the electrolyte.
[0038] A reasonable mass ratio of lithium difluorosulfonylimide in the electrolyte helps reduce the generation of hydrofluoric acid in the hybrid battery system, reduces the damage of hydrofluoric acid to the structure of lithium-containing transition metal oxide particles, and forms a dense and stable CEI film (positive electrode electrolyte interface film), improving the chemical stability of the CEI film, further blocking the dissolution of transition metal ions in the positive electrode active material, and reducing the probability of excessive corrosion of the current collector due to an excessively high mass ratio of lithium difluorosulfonylimide, thus improving the cycle stability of the hybrid battery cells.
[0039] In any embodiment, the mass percentage of lithium bis(fluorosulfonyl)imide is 0.1%-2% based on the total mass of the electrolyte.
[0040] The reasonable mass ratio of lithium difluorosulfonylimide in the electrolyte helps to further reduce the generation of hydrofluoric acid in the hybrid battery system, reduce the damage of hydrofluoric acid to the particle structure of lithium-containing transition metal oxides, and form a dense and stable CEI film (positive electrode electrolyte interface film), improve the chemical stability of the CEI film, further block the dissolution of transition metal ions in the positive electrode active material, and improve the cycle stability of the hybrid battery cells.
[0041] In any embodiment, the lithium difluorophosphate accounts for 1%-5% of the total mass of the electrolyte.
[0042] A reasonable mass ratio of lithium difluorophosphate in the electrolyte helps reduce the generation of hydrofluoric acid in the hybrid battery system, reduces the damage of hydrofluoric acid to the structure of lithium-containing transition metal oxide particles, and forms a dense and stable CEI film (positive electrode electrolyte interface film), improving the chemical stability of the CEI film, further blocking the dissolution of transition metal ions in the positive electrode active material, and reducing the probability of excessively high film-forming impedance due to an excessively high mass ratio of lithium difluorophosphate, thereby improving the cycle stability of the hybrid battery cells.
[0043] In any embodiment, the lithium difluorophosphate accounts for 2%-5% of the total mass of the electrolyte.
[0044] A reasonable mass ratio of lithium difluorophosphate in the electrolyte helps to further reduce the generation of hydrofluoric acid in the hybrid battery system, reduce the damage of hydrofluoric acid to the structure of lithium-containing transition metal oxide particles, and form a dense and stable CEI film (positive electrode electrolyte interface film), improve the chemical stability of the CEI film, further block the dissolution of transition metal ions in the positive electrode active material, and improve the cycle stability of the hybrid battery cell.
[0045] In any embodiment, the electrolyte comprises lithium hexafluorophosphate, and the mass percentage of lithium hexafluorophosphate is 5%-12% based on the total mass of the electrolyte.
[0046] Although lithium hexafluorophosphate hydrolyzes to produce hydrofluoric acid, it has high solubility and ionic conductivity in the electrolyte, which is beneficial for increasing the lithium-ion content in the electrolyte. At the same time, when the mass ratio of lithium hexafluorophosphate in the electrolyte is within a reasonable range, it is beneficial to improve the ionic conductivity of the electrolyte while reducing the amount of hydrofluoric acid generated, reducing the damage to the structure of lithium-containing transition metal oxide particles, and further improving the cycle performance of the hybrid system battery cells.
[0047] In any embodiment, the electrolyte includes a second component, which includes one or more of 1,3-propanesulfonyl lactone, lithium difluorooxalate borate, trimethylsilyl phosphate, lithium bis(oxalate borate), and vinyl sulfate; optionally, the second component includes 1,3-propanesulfonyl lactone.
[0048] The inclusion of a second component in the electrolyte is beneficial for forming a dense and stable SEI film, improving the chemical stability of the SEI film, reducing the damage of the SEI film by transition metal ions, reducing the loss of active lithium caused by rebuilding the SEI film, and improving the cycle stability of the hybrid system battery cells.
[0049] In any embodiment, the mass percentage of the second component is 0.2%-5% based on the total mass of the electrolyte.
[0050] When the mass ratio of the second component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film, improve the chemical stability of the SEI film, reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time reduce the probability of excessive film resistance caused by an excessively high mass ratio of the second component, thereby improving the cycle stability of the hybrid system battery cells.
[0051] In any embodiment, the second component accounts for 0.5%-3% of the total mass of the electrolyte.
[0052] When the mass ratio of the second component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film, improve the chemical stability of the SEI film, further reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and improve the cycle stability of the battery cells in the hybrid system.
[0053] In any embodiment, the mass percentage of the second component is 0.5%-1% based on the total mass of the electrolyte.
[0054] When the mass ratio of the second component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film, improve the chemical stability of the SEI film, further reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time take into account the interfacial impedance of the film formation, thus improving the cycle stability of the battery cells in the hybrid system.
[0055] In any embodiment, the electrolyte comprises a cyclic carbonate compound, and the cyclic carbonate compound accounts for 20%-45% of the total mass of the electrolyte.
[0056] The electrolyte contains a certain amount of cyclic carbonate compounds, which have a high dielectric constant. This is beneficial for improving the degree of lithium salt dissociation and ionic conductivity in the electrolyte, making it easier for lithium ions in the electrolyte to diffuse, reducing the probability of local lithium plating in the mixed system, and improving the cycle stability of the battery cells in the mixed system.
[0057] In any embodiment, the electrolyte comprises a cyclic carbonate compound, and the cyclic carbonate compound accounts for 18%-35% of the total mass of the electrolyte.
[0058] A reasonable mass ratio of cyclic carbonate compounds in the electrolyte is beneficial for improving the degree of lithium salt dissociation and ionic conductivity in the electrolyte, making it easier for lithium ions to diffuse in the electrolyte, reducing the probability of local lithium plating in the mixed system, and improving the cycle stability of the battery cells in the mixed system.
[0059] In any embodiment, the cyclic carbonate compound includes one or more of ethylene carbonate, propylene carbonate, and butene carbonate; optionally, the cyclic carbonate compound includes ethylene carbonate.
[0060] In any embodiment, the electrolyte comprises a chain carbonate compound, and the chain carbonate compound accounts for 40%-75% of the total mass of the electrolyte.
[0061] The electrolyte contains a certain amount of chain carbonate compounds, which have low viscosity. This helps to improve the electrolyte's wetting ability on the electrode and the lithium-ion transport rate, reduce the probability of localized excessive lithium-ion concentration and uneven lithium salt distribution in the hybrid battery system, and improve the cycle stability of the hybrid battery cells.
[0062] In any embodiment, the electrolyte comprises a chain carbonate compound, and the chain carbonate compound accounts for 50%-70% of the total mass of the electrolyte.
[0063] A reasonable mass ratio of chain carbonate compounds in the electrolyte is beneficial for improving the electrolyte's wetting ability on the electrode and the lithium-ion transport rate, reducing the probability of excessively high local lithium-ion concentration and uneven lithium salt distribution in the hybrid battery system, and improving the cycle stability of the hybrid battery cells.
[0064] In any embodiment, the chain carbonate compound includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methyl propyl carbonate; optionally, the chain carbonate includes ethyl methyl carbonate and diethyl carbonate.
[0065] In any embodiment, the electrolyte comprises ethyl methyl carbonate, and the mass percentage of ethyl methyl carbonate is 35%-55% based on the total mass of the electrolyte.
[0066] The electrolyte contains an appropriate amount of ethyl methyl carbonate, which has high stability and low viscosity. It can be adapted to the high-voltage environment of the hybrid battery cell, which is beneficial to improving the electrolyte's wetting ability on the electrode and the lithium-ion transport rate. It also reduces the probability of localized excessive lithium-ion concentration and uneven lithium salt distribution in the hybrid battery, and improves the cycle stability of the hybrid battery cell.
[0067] In any embodiment, the electrolyte comprises diethyl carbonate, and the mass percentage of diethyl carbonate is 10%-20% based on the total mass of the electrolyte.
[0068] The electrolyte contains an appropriate amount of diethyl carbonate, which has high stability and low viscosity. It can be adapted to the high-voltage environment of the hybrid battery cell, which is beneficial to improving the electrolyte's wetting ability on the electrode and the lithium-ion transport rate. It also reduces the probability of localized excessive lithium-ion concentration and uneven lithium salt distribution in the hybrid battery, and improves the cycle stability of the hybrid battery cell.
[0069] In any embodiment, the electrolyte includes a third component, which includes one or more of vinylene carbonate and fluoroethylene carbonate.
[0070] The electrolyte includes a third component that can form a dense and stable SEI film at the negative electrode, which helps to reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and improve the cycle stability of the hybrid system battery cells.
[0071] In any embodiment, the mass percentage of the third component is 0.08%-5% based on the total mass of the electrolyte.
[0072] When the mass proportion of the third component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film on the negative electrode, which helps to reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time reduce the probability of excessive film-forming impedance caused by an excessively high mass proportion of the third component, thereby improving the cycle stability of the hybrid system battery cells.
[0073] In any embodiment, the mass percentage of the third component is 0.5%-3% based on the total mass of the electrolyte.
[0074] When the mass proportion of the third component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film on the negative electrode, which helps to reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time reduce the probability of excessive film-forming impedance caused by an excessively high mass proportion of the third component, thereby improving the cycle stability of the hybrid system battery cells.
[0075] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn50 of the lithium-containing transition metal oxide particles is 1μm-4μm.
[0076] In hybrid battery cells, the negative electrode location corresponding to lithium transition metal oxide particles is prone to local lithium plating. This is because, compared to lithium transition metal phosphate particles, the region containing lithium transition metal oxide materials releases a large number of lithium ions per unit time, requiring the corresponding negative electrode side to bear a high concentration of lithium ion insertion, and even triggering local lithium plating. In this embodiment, by controlling the Dn50 of the lithium transition metal oxide particles within the above-mentioned range, it means that the particle size of the lithium transition metal oxide particles is smaller, which is beneficial to improving the uniformity of the distribution of lithium transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid battery cell.
[0077] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn50 of the lithium-containing transition metal oxide particles is 1μm-3μm.
[0078] Within a reasonable range, the Dn50 of lithium-containing transition metal oxide particles is beneficial to further improve the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0079] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn50 of the lithium-containing transition metal oxide particles is 1.5μm-2.5μm.
[0080] Within a reasonable range, the Dn50 of lithium-containing transition metal oxide particles is beneficial to further improve the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0081] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the particle size distribution concentration of the lithium-containing transition metal oxide particles (Dn90-Dn10) / Dn50 is 0.6-2.
[0082] The particle size distribution concentration of lithium-containing transition metal oxide particles is within a suitable range, indicating that the particle size is highly consistent. This reduces the specific capacity difference in different regions of the positive electrode active material layer, thereby reducing the phenomenon of local lithium-ion concentration concentration, alleviating local lithium plating, and further improving the cycle stability of the hybrid system battery cell.
[0083] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the particle size distribution concentration of the lithium-containing transition metal oxide particles (Dn90-Dn10) / Dn50 is 0.8-1.8.
[0084] The particle size distribution concentration of lithium-containing transition metal oxide particles is within a suitable range, which is beneficial to further reduce the difference in specific capacity in different regions of the positive electrode active material layer, thereby reducing the phenomenon of local lithium-ion concentration concentration, alleviating local lithium plating, and further improving the cycle stability of the hybrid system battery cell.
[0085] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn10 of the lithium-containing transition metal oxide particles is 0.5μm-2μm.
[0086] The Dn10 of lithium-containing transition metal oxide particles within the above range is beneficial to reducing the particle size of lithium-containing transition metal oxide particles, improving the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0087] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn10 of the lithium-containing transition metal oxide particles is 0.5μm-1.5μm.
[0088] When the Dn10 of lithium-containing transition metal oxide particles is within a suitable range, it is beneficial to reduce the particle size of lithium-containing transition metal oxide particles, improve the uniformity of distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0089] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn90 of the lithium-containing transition metal oxide particles is 2.5μm-5μm.
[0090] The Dn90 of lithium-containing transition metal oxide particles within the above range is beneficial to reducing the particle size of lithium-containing transition metal oxide particles, improving the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0091] In any embodiment, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn90 of the lithium-containing transition metal oxide particles is 3μm-4μm.
[0092] The Dn90 of lithium-containing transition metal oxide particles within the above range is beneficial to reducing the particle size of lithium-containing transition metal oxide particles, improving the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0093] In any embodiment, the proportion of nickel moles is 50%-80% based on the total number of moles of nickel, cobalt and M in the lithium-containing transition metal oxide particles.
[0094] Increasing the nickel content in lithium-containing transition metal oxide particles helps to increase specific capacity while lowering the upper limit of its operating voltage. In the embodiments of this application, the nickel content in the lithium-containing transition metal oxide particles within the above-mentioned range helps to reduce the charging cut-off voltage of the hybrid system battery cell, reduce the voltage range difference between lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles, alleviate load shunting phenomenon, and improve the cycle stability of the hybrid system battery cell.
[0095] In any embodiment, based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles, the molar percentage of cobalt is 5%-20%.
[0096] Cobalt can enhance the order and stability of the lattice of lithium-containing transition metal oxide particles. Based on the total molar number of nickel, cobalt and M elements in lithium-containing transition metal oxide particles, the molar proportion of cobalt within the above range is beneficial to improving the stability of lithium-containing transition metal oxide particles and improving the cycle stability of hybrid battery cells.
[0097] In any embodiment, based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles, the molar percentage of the M element is 15%-40%.
[0098] In any embodiment, the lithium-containing transition metal oxide particles are single-crystal particles.
[0099] The lithium-containing transition metal oxide particles are single-crystal particles, meaning that their overall crystal is continuous and there are no grain boundary structures inside. This can effectively reduce stress concentration during charging and discharging and inhibit particle cracking, thereby improving the cycle stability of the hybrid battery cell.
[0100] In any embodiment, based on the total mass of the positive electrode active material, the mass percentage of the lithium-containing transition metal oxide particles is 50%-90%.
[0101] Having the mass percentage of lithium transition metal oxide particles within the above range is beneficial for improving the energy density of hybrid battery cells while taking into account the manufacturing cost of hybrid battery cells.
[0102] In any embodiment, based on the total mass of the positive electrode active material, the mass percentage of the lithium-containing transition metal oxide particles is 60%-80%.
[0103] A reasonable mass ratio of lithium transition metal oxide particles is beneficial for further improving the energy density of hybrid battery cells while taking into account the manufacturing cost of hybrid battery cells.
[0104] In any embodiment, the lithium-containing transition metal oxide particles include one or more of lithium-containing nickel-cobalt-manganese oxide particles and their doped and / or coated modified materials, and lithium-containing nickel-cobalt-aluminum oxide particles and their doped and / or coated modified materials.
[0105] In any embodiment, the lithium-containing transition metal phosphate particles include a particle body and a carbon material disposed on at least a portion of the surface of the particle body.
[0106] In any embodiment, the thickness of the carbon material is 2nm-25nm.
[0107] Within the aforementioned range, the thickness of the carbon material on the surface of lithium transition metal phosphate particles is beneficial for improving the electronic conductivity of lithium transition metal phosphate particles, enhancing their kinetic performance, reducing the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reducing the probability of lithium transition metal oxide particles breaking and surface structure collapsing due to current overload, and improving the cycle stability of the hybrid battery cell.
[0108] In any embodiment, the carbon material accounts for 0.5%-3% of the total mass of the lithium transition metal phosphate particles.
[0109] When the mass percentage of carbon in lithium transition metal phosphate particles is within the above range, it is beneficial to improve the electronic conductivity of lithium transition metal phosphate particles, improve their kinetic performance, reduce the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reduce the probability of lithium transition metal oxide particles breaking and surface structure collapse due to current overload, and improve the cycle stability of the hybrid battery cell.
[0110] In any embodiment, the lithium-containing transition metal phosphate particles comprise the components represented by the following general formula I: Li m1 Fe x1 Mn y1 M1 b1 P z1 Q1 c1 O n1 N1 d1 Formula I, wherein 0.8≤m1≤1.2, 0<x1<1, 0<y1<1, 0.9≤x1+y1≤1, 0.95≤z1≤1, 3.5≤n1≤4, 0≤b1≤0.1, 0≤c1≤0.1, 0≤d1≤0.1; wherein M1 includes one or more of Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, and Ti, Q1 includes one or more of B, S, Si, and N, and N1 includes one or more of F, Cl, and Br.
[0111] Selecting appropriate modifying elements can improve the ion diffusion pathway of lithium-containing transition metal phosphate particles, increase the lithium-ion diffusion rate of lithium-containing transition metal phosphate particles, reduce the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reduce the probability of lithium-containing transition metal oxide particles breaking and surface structure collapse due to current overload, and improve the cycle stability of the hybrid battery cell.
[0112] In any embodiment, the positive electrode active material layer includes a first conductive agent, which includes a dotted conductive agent, and the dotted conductive agent includes one or more of Super P, Ketjen Black, acetylene black, and conductive graphite.
[0113] In any embodiment, based on the total mass of the positive electrode active material layer, the mass percentage of the dot-shaped conductive agent is 0.2%-2.0%.
[0114] In any embodiment, the first conductive agent further includes a linear conductive agent, which includes one or more of carbon nanotubes, vapor-grown carbon fibers, and carbon nanofibers; optionally, the first conductive agent includes carbon nanotubes.
[0115] The combined use of dot-like and linear conductive agents balances both long-range and short-range conductivity, which is beneficial for further improving the conductive network in the positive electrode active material layer.
[0116] In any embodiment, the mass percentage of the linear conductive agent is 0.05%-1.5% based on the total mass of the positive electrode active material layer.
[0117] In any embodiment, the mass percentage of the linear conductive agent is 0.05%-1.25% based on the total mass of the positive electrode active material layer.
[0118] In any embodiment, the positive electrode sheet includes a positive electrode film layer disposed on at least one side of the positive electrode current collector, the positive electrode film layer including the positive electrode active material layer and a positive electrode undercoating layer disposed between the positive electrode active material layer and the positive electrode current collector; the positive electrode undercoating layer includes a first polymer and a second conductive agent.
[0119] In any embodiment, the thickness of the positive electrode undercoat is 0.5 μm-5 μm.
[0120] In any embodiment, the compaction density of the positive electrode film is 2.60 g / cm³. 3 -3.4g / cm 3 .
[0121] Within the aforementioned range, the compaction density of the cathode film ensures a high packing density of the active material, achieving a high volumetric energy density, while maintaining a suitable pore structure, which is beneficial for electrolyte wetting and lithium-ion transport. This achieves both high energy density and improved kinetic performance of the cathode film.
[0122] In any embodiment, the electrode assembly includes a negative electrode sheet, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector, the negative active material layer includes a negative active material, the negative active material includes graphite, and the volume distribution particle size Dv50 of the negative active material is 7μm-15μm.
[0123] In the embodiments of this application, controlling the volume distribution particle size Dv50 of graphite in the negative electrode active material within a suitable range is beneficial to increasing the lithium-ion insertion port, shortening the lithium-ion diffusion path, thereby improving the lithium-ion insertion rate, reducing local lithium plating, and improving the cycle stability of the hybrid system battery cell.
[0124] In any embodiment, the volume distribution particle size Dv50 of the negative electrode active material is 8μm-13μm.
[0125] In the embodiments of this application, controlling the volume distribution particle size Dv50 of graphite in the negative electrode active material within a suitable range is beneficial to increasing the lithium-ion insertion port and shortening the lithium-ion diffusion path, thereby improving the lithium-ion insertion rate and reducing local lithium plating. At the same time, controlling the specific surface area of graphite reduces the probability of exacerbating electrolyte side reactions due to excessive specific surface area of graphite, and improves the cycle stability of the hybrid system battery cell.
[0126] In any embodiment, the electrode assembly further includes a separator disposed on at least one side of the positive electrode sheet. The separator includes a base film, a first coating disposed on both sides of the base film, and a second coating disposed between the first coating and the base film. Optionally, the second coating is disposed near the positive electrode sheet. The first coating includes a second polymer, and the second coating includes inorganic particles and a third polymer.
[0127] The first coating comprises a polymer with good adhesion, which helps to improve the adhesion of the separator. The second coating is further disposed on the side of the base film close to the positive electrode, which helps to reduce the direct contact between the base film and the positive electrode active material, reduce the damage to the base film caused by byproducts generated by the electrolyte at the positive electrode active material, thereby improving the stability of the separator and further improving the cycle stability of the hybrid battery cell.
[0128] In any embodiment, the second polymer and the third polymer each independently include one or more of fluoropolymers and acrylate polymers.
[0129] In any embodiment, the fluoropolymer includes a vinylidene fluoride polymer, which includes one or more of vinylidene fluoride homopolymers, copolymers of vinylidene fluoride and tetrafluoroethylene, copolymers of vinylidene fluoride and hexafluoropropylene, and copolymers of vinylidene fluoride and trifluoroethylene.
[0130] In any embodiment, the acrylate polymer includes an acrylate-acrylonitrile-acrylamide-propylene copolymer.
[0131] In any embodiment, the inorganic particles include one or more of alumina, boehmite, silicon dioxide, cerium oxide, magnesium aluminate, zirconium oxide, and titanium dioxide.
[0132] In any embodiment, the rated cutoff voltage of the battery cell is 4.25V-4.45V.
[0133] In any embodiment, the housing further includes an end cap, and the ratio of the size of the first portion to the size of the end cap is 0.35-0.80 along the thickness direction of the battery cell.
[0134] Along the thickness direction of the battery cell, the ratio of the size of the first part to the size of the end cap is within the above range, which is beneficial to increase the area of the first part, thereby increasing the solderable area of the tab and electrode terminal, reducing connection resistance, reducing heat generation, further improving the temperature distribution uniformity of the positive electrode active material layer, thereby reducing the probability of manganese ion dissolution from lithium transition metal phosphate particles, reducing the damage of manganese ions to the SEI film, reducing the consumption of active lithium ions, and improving the cycle stability of the hybrid system battery cell.
[0135] In any embodiment, the ratio of the size of the first portion to the size of the end cap is 0.50-0.80 along the thickness direction of the battery cell.
[0136] Along the thickness direction of the battery cell, the ratio of the size of the first part to the size of the end cap is within the above range, which is beneficial to further increase the area of the first part, further increase the solderable area of the tab and electrode terminal, reduce connection resistance, reduce heat generation, further improve the temperature distribution uniformity of the positive electrode active material layer, thereby reducing the probability of manganese ion dissolution of lithium transition metal phosphate particles, reducing the damage of manganese ions to the SEI film, reducing the consumption of active lithium ions, and improving the cycle stability of the hybrid system battery cell.
[0137] A second aspect of this application provides a battery device comprising the battery cell described in the above embodiments, wherein the battery device includes one or more of a battery module, a battery pack, and an energy storage battery.
[0138] A third aspect of this application provides an electrical device that includes the battery device described in the above embodiments, the battery device being used to provide electrical energy.
[0139] A fourth aspect of this application provides an energy storage device that includes the battery device described in the above embodiments, the battery device being used to store electrical energy.
[0140] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0141] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0142] Figure 1 This is a state-of-charge (SOC-V) curve of a single battery cell under charging according to an embodiment of this application; Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application; Figure 3 yes Figure 2 An exploded view of a battery cell according to one embodiment of this application is shown. Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application; Figure 5 yes Figure 4 The diagram shown is a structural schematic of a battery module according to one embodiment of this application; Figure 6 This is a schematic diagram of an electrical device in which a single battery cell is used as a power source according to one embodiment of this application.
[0143] Figure label: M, length direction of battery module; X, thickness direction of battery cell; E, first direction; F, second direction; 2, battery pack; 5, housing; 5a, first housing section; 5b, second housing section; 5c, storage space; 6, battery module; 7, battery cell; 70, first battery pack; 10, electrode assembly; 111, first tab; 121, second tab; 20, outer casing; 21, housing; 22, end cap; 31, first electrode terminal; 32, second electrode terminal. Detailed Implementation
[0144] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0145] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0146] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0147] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0148] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0149] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0150] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0151] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0152] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0153] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0154] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0155] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0156] Unless otherwise stated, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.
[0157] Lithium-containing transition metal phosphate particles offer advantages such as low cost and high safety as positive electrode active materials, but their specific capacity is significantly lower than that of lithium-containing transition metal oxides with layered structures. The combined use of these two materials in the positive electrode can improve the energy density of the battery cell while maintaining cost advantages. However, experimental results show that battery cells using a mixture of these two materials as the positive electrode active material (referred to as hybrid system battery cells) do not have ideal cycle performance compared to single-system battery cells. Therefore, improving the cycle performance of batteries while maintaining low cost and high energy density has become a pressing technical problem to be solved in this field.
[0158] To address the aforementioned problems, this application provides a battery cell 7, comprising a housing 20, electrode terminals (first electrode terminal 31, second electrode terminal 32), an electrode assembly 10, and an electrolyte. The housing 20 has an internal cavity and a through hole communicating with the inside and outside of the cavity. The first electrode terminal 31 and the second electrode terminal 32 each comprise a first portion and a second portion. The first portion is entirely located within the cavity, and the second portion extends through the through hole and is partially located outside the cavity. The first and second portions are integrally formed. The electrode assembly 10 and the electrolyte are disposed within the cavity. The electrode assembly 10 includes an electrode sheet and tabs (first tab 111, second tab 121), with the first tab 111 and second tab 121 directly connected to the first portion. The electrode sheet includes a positive electrode sheet, which includes a positive current collector and a positive active electrode disposed on at least one side of the positive current collector. The material layer, the positive electrode active material layer includes positive electrode active material, which includes lithium transition metal oxide particles and lithium transition metal phosphate particles; the lithium transition metal oxide particles include nickel, cobalt, and M elements, where M elements include manganese and / or aluminum; the lithium transition metal phosphate particles include iron and manganese; based on the total molar number of manganese and iron elements in the lithium transition metal phosphate particles, the molar number of manganese is 40%-75%; in the cross section along the thickness direction of the positive electrode active material layer, the Dn50 of the lithium transition metal phosphate particles is 100nm-300nm, and the Dn90 of the lithium transition metal phosphate particles is 250nm-500nm, where Dn50 and Dn90 refer to the particle size corresponding to 50% and 90% of the cumulative particle number distribution curve.
[0159] The positive electrode active material includes lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles. The lithium-containing transition metal oxide particles include nickel, cobalt, and M elements, with M elements including manganese and / or aluminum. The lithium-containing transition metal phosphate particles include iron and manganese. The molar percentage of manganese in the lithium-containing transition metal phosphate particles is 40%-75%, and the Dn50 of the lithium-containing transition metal phosphate particles is 100nm-300nm, and the Dn90 is 250nm-500nm. When the tabs on the electrode assembly are directly connected to the first part of the electrode terminal, it is beneficial to improve the cycle stability of the hybrid system battery cell.
[0160] Using a mixture of lithium transition metal phosphate particles and lithium transition metal oxide particles as the positive electrode active material helps to balance the manufacturing cost and energy density of the battery cell. To fully utilize the specific capacity of the lithium transition metal oxide particles and improve the energy density of the battery cell, the charging cutoff voltage of the battery cell needs to be set to around 4.25V. The main discharge voltage range of the lithium transition metal oxide particles is significantly higher than that of the lithium transition metal phosphate particles. This means that the lithium transition metal phosphate particles mainly bear the main lithium-ion supply in the low-voltage range, while the lithium transition metal oxide particles mainly bear the main lithium-ion supply in the high-voltage range. This results in both materials experiencing an equivalent rate load much higher than the apparent rate in their corresponding operating ranges, i.e., load shunting. Therefore, even at low rates of charge and discharge, the load shunting phenomenon in the hybrid battery cell still causes rapid lithium-ion insertion / extraction within the positive electrode active material. The structural stability of the lithium transition metal oxide is poor, and it is easily affected by load shunting during cycling, which is significantly detrimental to its structural integrity. Sustained current overload can easily trigger irreversible phase transitions in lithium-containing transition metal oxide particles. Simultaneously, the rapid and non-uniform insertion / extraction of lithium ions at high current densities leads to a severe mismatch between the surface and bulk lattice parameters of the lithium-containing transition metal oxide particles, generating enormous internal stress within the particles. This triggers the initiation and propagation of grain boundary microcracks, ultimately causing particle breakage and surface structure collapse, resulting in decreased cycle stability of the hybrid battery cells. Therefore, reducing the current loaded by lithium-containing transition metal oxides has become crucial for improving the cycle stability of hybrid systems.
[0161] Compared to lithium iron phosphate, lithium transition metal phosphate particles, which contain both manganese and iron, can mitigate the voltage mismatch between the two materials by utilizing two voltage platforms. However, when the molar proportion of manganese in lithium transition metal phosphate particles is less than 40%, the capacity of these particles in the high-voltage range is reduced, hindering their compatibility with lithium transition metal oxide particles at high voltages and failing to effectively alleviate load shunting. While a molar proportion of manganese in lithium transition metal phosphate particles greater than 75% improves voltage platform compatibility, significant manganese ion dissolution still negatively impacts the cycle stability of the hybrid battery cells.
[0162] like Figure 1 As shown, controlling the molar proportion of manganese in lithium transition metal phosphate particles to 40%-75% results in a high degree of matching between manganese and lithium transition metal oxide particles under high voltage, which can reduce the impact of high voltage ( Figure 1 The discharge voltage range under medium and high voltage conditions is used to control the current of lithium transition metal oxide loads, while also controlling the degree of manganese ion dissolution within a reasonable range.
[0163] However, lithium-containing transition metal phosphate particles have low electronic conductivity and lithium-ion diffusion coefficient, resulting in poor intrinsic kinetic performance. Furthermore, when the molar proportion of manganese is 40%-75%, manganese ions will cause significant distortion, leading to the distortion of lithium-ion diffusion channels and further reducing the kinetic performance of lithium-containing transition metal phosphate particles.
[0164] During the charging and discharging process of a hybrid battery cell, lithium-containing transition metal phosphate particles with slow lithium-ion diffusion cannot complete charge transfer and lithium-ion intercalation / deintercalation in time. This causes the charging and discharging current to concentrate on lithium-containing transition metal oxide particles with better kinetics. As a result, lithium-containing transition metal phosphate particles still cannot effectively share the current, causing lithium-containing transition metal oxide particles to bear a high rate of current density even at a higher voltage than 3.7V.
[0165] By employing lithium transition metal phosphate particles containing iron and manganese, and controlling the molar ratio of manganese in the lithium transition metal phosphate particles to be greater than 40%-75%, and simultaneously matching the particles with a Dn50 of 100nm-300nm and a Dn90 of 250nm-500nm, the kinetic performance of the lithium transition metal phosphate particles and the voltage plateau matching with the lithium transition metal oxide particles can be balanced, thereby alleviating the load shunting phenomenon and improving the cycle stability of the hybrid battery system.
[0166] It is worth mentioning that the applicant discovered that the content of small particles in the positive electrode active material layer has a crucial impact on alleviating the load shunting phenomenon. As shown in Table 2, when the Dn50 of the lithium transition metal phosphate particles is 100nm-300nm but the Dn90 is greater than 500nm, it means that the lithium transition metal phosphate particles still contain a lot of large particles with insufficient kinetic performance. Most of the charge and discharge current still tends to concentrate in the lithium transition metal oxide particles with better kinetics, and cannot effectively alleviate the load shunting phenomenon.
[0167] However, small-sized lithium-containing transition metal phosphate particles have a large specific surface area, which can easily exacerbate the dissolution of manganese ions under high-temperature conditions. The manganese ions further dissolve in the electrolyte and are reduced and precipitated at the negative electrode, which can easily damage the solid electrolyte interphase (SEI) membrane. As a result, more active lithium is consumed during the SEI membrane repair process, which has an adverse effect on the cycle stability of the hybrid battery cells.
[0168] In this embodiment, the tabs on the electrode assembly are directly connected to the first part of the electrode terminal. Combined with the above-mentioned hybrid system, the impedance and heat generation at the tabs are reduced, the heat at the maximum heat generation point of the battery cell is reduced, the temperature distribution uniformity of the positive electrode active material layer is improved, the temperature rise of the positive electrode sheet is reduced, thereby reducing the probability of manganese ion dissolution of lithium transition metal phosphate particles, reducing the damage of manganese ions to the SEI film, reducing the consumption of active lithium ions, and improving the cycle stability of the hybrid system battery cell.
[0169] In some embodiments, the lithium-containing transition metal oxide particles include nickel, cobalt, and M, wherein the M element includes manganese.
[0170] In some embodiments, the lithium-containing transition metal oxide particles include nickel, cobalt, and M, wherein the M element includes aluminum.
[0171] In this application, lithium transition metal phosphate particles refer to phosphate materials containing lithium, and lithium transition metal oxide particles refer to oxide materials containing lithium. Both can be detected by any method known in the art. For example, they can be detected by combining X-ray diffraction (XRD) with energy dispersive spectroscopy (EDS) or inductively coupled plasma mass spectrometry (ICP-MS).
[0172] It should be noted that the lithium-containing transition metal oxide particles referred to in this article include, but are not limited to, nickel-cobalt-manganese-based lithium-containing oxide particles, nickel-cobalt-aluminum-based lithium-containing oxide particles, and their doped and coated modified materials. The lithium-containing transition metal phosphate particles referred to in this article include, but are not limited to, doped and / or coated modified materials of lithium-containing transition metal phosphate particles.
[0173] In this application, the term "particle" refers to a particle in the positive electrode active material layer that has a recognizable complete boundary in the field of view at a certain magnification, such as 10,000x. Defects and scratches may exist inside the particle, but a complete boundary sufficient to divide the particle cannot be identified inside the particle.
[0174] In this application, lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles in the positive electrode active material layer can be specifically identified by the following method: Disassemble the battery to obtain the positive electrode sheet, and cut the positive electrode active material layer along the thickness direction of the electrode sheet using an argon ion beam (as an example, the equipment model can be: Leica EMTIC3XCP, working voltage: 6kV, working time: 6h). After exposing the cut surface, use a scanning electron microscope (as an example, the equipment model can be: Hitachi SU8230, working voltage: 3kV, beam current: high, probe model: U (LA100), working distance <5mm) to observe the cut surface of the positive electrode active material layer along the thickness direction of the electrode sheet.
[0175] Images were acquired using a scanning electron microscope (SEM) at non-edge locations within the cross-section of the positive electrode active material layer (after observing the electrode edge under the SEM, the field of view was adjusted to the center of the sample) in secondary electron mode. Electron micrographs were taken at 10kx magnification, and EDS (energy dispersive spectroscopy) was used to scan the SEM images. The particles were identified and distinguished by identifying characteristic elements (such as P and Ni) in lithium transition metal phosphate particles and lithium transition metal oxide particles. For example, based on the distribution spectrum of P in the test area, particles where P was not clearly visible were identified as lithium transition metal oxide particles, while particles clearly visible were identified as lithium transition metal phosphate particles.
[0176] The positive electrode used for testing can be a prepared positive electrode or a positive electrode disassembled from a fully discharged battery.
[0177] In this application, the fully discharged state refers to placing the battery cell at 25°C, letting it stand for 2 hours, maintaining the battery temperature at 25°C, discharging the battery at a constant current of 1 / 3C to 2.0V, letting it stand for 30 minutes, and then discharging it at a constant current of 0.04C to 2.0V.
[0178] In this application, based on the total molar number of manganese and iron in lithium transition metal phosphate particles, the molar percentage of manganese can be specifically tested using the following method: Disassemble the battery cell to obtain the positive electrode sheet. Cut the positive electrode sheet into 6mm × 6mm samples using ceramic scissors, attach them to a sample stage coated with paraffin wax, ensuring the sample protrudes slightly (<1mm) from the edge of the sample stage. Then, turn on the power of the argon ion cross-section polisher (JEOL IB-09010 CP type argon ion cross-section polisher from Japan) and apply a vacuum (10⁻⁷ Pa). Adjust the parameters, and then use the polisher to cut the positive electrode test film layer along the thickness direction of the sample. After exposing the cut surface, use a scanning electron microscope to observe the cross-section of the positive electrode sheet along the thickness direction. Observe the positive current collector and the positive active material layers on both sides of the positive current collector under the scanning electron microscope. Then, adjust the field of view to the positive active material layer, and use the field of view area as the test area. Electron microscopy (SEM) images were taken to obtain scanning electron microscope (SEM) images of the cross-section of the positive electrode active material layer along the thickness direction of the positive electrode sheet. Energy dispersive spectroscopy (EDS) was performed on the test area. Based on the distribution spectrum of phosphorus (P) in the test area, the region clearly showing P was magnified. The particle composition was determined by EDS, identifying it as lithium transition metal phosphate particles. Selected lithium transition metal phosphate particles were subjected to EDS testing to obtain the molar percentage of each element in the particles. This was converted to calculate the molar percentage of manganese based on the total molar number of manganese and iron in the lithium transition metal phosphate particles. At least 500 particles were measured, and the average value was taken as the test result.
[0179] In some embodiments, based on the total number of moles of manganese and iron in the lithium transition metal phosphate particles, the molar percentage of manganese can be selected as 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, or any value range between the two.
[0180] When the molar percentage of manganese in lithium transition metal phosphate particles is less than 40%, the capacity of lithium transition metal phosphate particles in the high voltage range is low, which is not conducive to matching the voltage platform of lithium transition metal oxide particles. The two types of materials are prone to load shunting due to step charge and discharge. When the molar percentage of manganese in lithium transition metal phosphate particles is greater than 75%, the degree of manganese ion dissolution is large. Manganese ions dissolve in the electrolyte and are reduced and precipitated at the negative electrode, which easily damages the solid electrolyte interphase (SEI) film. As a result, more active lithium is consumed in the SEI film repair process, which will deteriorate the cycle stability of the hybrid system battery cells.
[0181] In this application, the Dn50 and Dn90 of lithium transition metal phosphate particles in the cross-section along the thickness direction of the positive electrode active material layer can be specifically tested using the following method: Disassemble the battery to obtain the positive electrode sheet. After distinguishing between lithium transition metal oxide particles and lithium transition metal phosphate particles in the cross-section along the thickness direction of the positive electrode active material layer using the method described above, locate the lithium transition metal phosphate particle region and analyze the lithium transition metal phosphate particles in the electron microscope image using ImageJ software (1.46r, win64 version). The specific method for using ImageJ software is as follows: Load the scanning electron microscope image to be analyzed; use the Cellpose plugin software to identify the particles, and then manually correct or label the lithium transition metal phosphate particles; finally, use ImageJ to read and analyze the data.
[0182] The specific method for identifying particles using the Cellpose plugin software is as follows: Set the segmentation diameter parameter (diameter in the Segmentation module) to 15 pixels, click "runcyto3" to perform particle identification; manually mark the particles in the image that were not identified by the software, were not fully identified by the software, or had identification errors. The particles that were not identified by the software, were not fully identified by the software, or had identification errors mainly include the following: 1. Particles that are too large or have scratches on their surface, making them unidentifiable or incompletely identifiable; 2. During argon ion beam cutting, scratches may be generated on the particle surface, and the software may misjudge these scratches as particle boundaries during identification, leading to identification errors; 3. Particles that are too small and were not successfully identified; 4. Particles located at the edge of the electron microscope field of view, with the particle's interior penetrated by the edge, preventing a complete display of the morphology, and resulting in identification errors due to partial identification replacing the whole. For the unidentified or misidentified particles mentioned above, manual calibration is performed. The specific process is as follows: 1. Delete large particles located around the edges of the scanning electron microscope that are not fully displayed. 2. Determine if any unidentified or misidentified particles have internal cracks or scratches. If no cracks or scratches are found, classify it as a single particle and manually mark it based on the observed particle boundary. 3. If cracks or scratches are found inside the particle, determine if they penetrate the particle. If not, classify it as a single particle and manually mark it. 4. If cracks or scratches penetrate the particle, determine if they are linear or irregular. 5. If the cracks or scratches are irregular, classify them as the boundary between particles and divide the particles along this boundary. 6. If the cracks or scratches are linear, perform contrast comparison. 7. If the contrast is not obvious and there is no crack-like appearance, classify it as a scratch and mark it as a single particle. 8. If the contrast is strong and there is a crack-like appearance, classify it as the boundary between particles and mark it as two particles. After manual marking, delete information irrelevant to the particles from the automatic image processing, thus completing the particle identification and marking in the image.
[0183] The "Feret" parameter of lithium transition metal phosphate particles obtained from statistical analysis is used as the particle size. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. Since particles smaller than 50 nm have a large error in the statistical process and are difficult to accurately identify, and the particle size of conductive agents is generally smaller than 50 nm, which would introduce a large error into the statistical results, particles smaller than 50 nm are not counted in the particle size statistics of this application. Following the above method, to ensure a statistically significant sample size, at least 10 non-overlapping scanning electron microscope images were acquired for each electrode. The particle size of at least 500 lithium transition metal phosphate particles was statistically analyzed. After obtaining all the measurement data, they were arranged in ascending order. The value at the median position was taken as the particle size Dn50 of the lithium transition metal phosphate particles, meaning that 50% of the particles have a particle size no larger than this value and 50% of the particles have a particle size no smaller than this value. The value at the 90% cumulative position was taken as the particle size Dn90 of the lithium transition metal phosphate particles, meaning that 90% of the particles have a particle size no larger than this value.
[0184] In some embodiments, the Dn50 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the electrode thickness direction can be selected as 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 175nm, 180nm, 185nm, 190nm, 195nm, 200nm, 205nm, 210nm, 215nm, 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, 250nm, 255nm, 260nm, 265nm, 270nm, 275nm, 280nm, 285nm, 290nm, 295nm, 300nm, or any value range between the two.
[0185] When the Dn50 of lithium transition metal phosphate particles in the cross-section along the thickness direction of the positive electrode active material layer is less than 100 nm, it means that the particle size of lithium transition metal phosphate particles is small. Their large specific surface area intensifies the dissolution of manganese ions at high temperatures. Manganese ions further dissolve in the electrolyte and are reduced and precipitated at the negative electrode, which easily damages the solid electrolyte interphase (SEI) film, causing more active lithium to be consumed during the SEI film repair process. When the Dn50 of lithium transition metal phosphate particles in the cross-section along the thickness direction of the positive electrode active material layer is greater than 300 nm, it means that the particle size of lithium transition metal phosphate particles is large. The lithium ion transport path increases, which is insufficient to improve the kinetic performance of lithium transition metal phosphate particles. It cannot effectively match the kinetic performance of lithium transition metal oxide particles. Lithium transition metal oxide particles are prone to particle breakage and surface structure collapse due to current overload, which will adversely affect the cycle stability of the hybrid system battery cells.
[0186] In some embodiments, the Dn90 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the electrode thickness direction can be selected as 250nm, 255nm, 260nm, 265nm, 270nm, 275nm, 280nm, 285nm, 290nm, 295nm, 300nm, 305nm, 310nm, 315nm, 320nm, 325nm, 330nm, 335nm, 340nm, 345nm, 350nm, 355nm, 360nm, etc. nm, 365nm, 370nm, 375nm, 380nm, 385nm, 390nm, 395nm, 400nm, 405nm, 410nm, 415nm, 420nm, 425nm, 430nm, 435nm, 440nm, 445nm, 450nm, 455nm, 460nm, 465nm, 470nm, 475nm, 480nm, 485nm, 490nm, 495nm, 500nm, or any range between two of these values.
[0187] When the Dn50 of lithium transition metal phosphate particles in the cross-section along the thickness direction of the positive electrode active material layer is 100nm-300nm, but the Dn90 is less than 250nm, it means that there is an excessive amount of small particles in the lithium transition metal phosphate particles. This increases the specific surface area of most lithium transition metal phosphate particles, leading to accelerated dissolution of manganese ions at high temperatures. The manganese ions further dissolve in the electrolyte and are reduced and precipitated at the negative electrode, easily damaging the solid electrolyte interphase (SEI) film, resulting in more active lithium being released from the SEI. The I film is consumed during the repair process; when the Dn50 of lithium transition metal phosphate particles in the cross section along the thickness direction of the positive electrode active material layer is 100nm-300nm, but the Dn90 of lithium transition metal phosphate particles is greater than 500nm, it means that there are still many large particles with insufficient kinetic performance in the lithium transition metal phosphate particles. Most of the charge and discharge current is still concentrated in the lithium transition metal oxide particles with better kinetics, which cannot effectively alleviate the load shunting phenomenon and is not conducive to improving the cycle stability of the hybrid system battery cell.
[0188] In some embodiments, the molar percentage of manganese is 45%-75%, based on the total molar number of manganese and iron in the lithium transition metal phosphate particles.
[0189] The molar ratio of manganese in lithium transition metal phosphate particles is within a reasonable range, which helps to reduce the dissolution of manganese ions, reduce the probability of manganese ions being reduced and precipitated at the negative electrode and causing damage to the SEI film, reduce the consumption of active lithium ions, and improve the cycle stability of the hybrid system battery cells.
[0190] In some embodiments, the molar percentage of manganese is 50%-70% based on the total molar number of manganese and iron in the lithium transition metal phosphate particles.
[0191] The molar proportion of manganese in lithium transition metal phosphate particles is within a reasonable range, which is beneficial to improving the plateau voltage contributed by manganese, improving the matching degree between its voltage plateau and that of lithium transition metal oxide particles, alleviating the load shunting phenomenon caused by the step charging and discharging of the two types of materials, and improving the cycle stability of the hybrid system battery cells.
[0192] In some embodiments, the Dn50 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 100nm-250nm.
[0193] In the cross-section along the thickness direction of the positive electrode active material layer, the Dn50 of the lithium transition metal phosphate particles is within a reasonable range. Further reducing the particle size of the lithium transition metal phosphate particles is beneficial to reducing the lithium-ion transport path, improving the kinetic performance of the lithium transition metal phosphate particles, reducing the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reducing the probability of lithium transition metal oxide particles breaking and surface structure collapse due to current overload, and improving the cycle stability of the hybrid battery cell.
[0194] In some embodiments, the Dn90 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 260nm-400nm.
[0195] In the cross-section along the thickness direction of the positive electrode active material layer, the Dn90 of the lithium transition metal phosphate particles is within a reasonable range, which can further balance the lithium ion transport path and the specific surface area of the lithium transition metal phosphate particles. This is beneficial to improving the kinetic performance of the lithium transition metal phosphate particles, reducing the degree of mismatch between the kinetic performance of the two types of materials in the hybrid battery cell, and reducing the probability of manganese ion dissolution of small-diameter lithium transition metal phosphate particles at high temperatures, thus comprehensively improving the cycle stability of the hybrid battery cell.
[0196] In some embodiments, in the cross section of the positive electrode active material layer along the electrode thickness direction, the Dn10 of the lithium transition metal phosphate particles is 70nm-130nm, where Dn10 refers to the particle size corresponding to the cumulative number of particles being 10% in the cumulative distribution curve of particle number.
[0197] In this application, the "Dn10 of lithium transition metal phosphate particles" is detected by referring to the method of "Dn50 of lithium transition metal phosphate particles" mentioned above. The difference is that after obtaining the particle size of at least 500 lithium transition metal phosphate particles, they are arranged in ascending order, and the value at the 10% cumulative position is taken as the particle size Dn10, that is, the particle size of 10% of the particles is not greater than this value.
[0198] In some embodiments, the Dn10 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the electrode thickness direction can be selected as 70nm, 72nm, 74nm, 76nm, 78nm, 80nm, 82nm, 84nm, 86nm, 88nm, 90nm, 92nm, 94nm, 96nm, 98nm, 100nm, 102nm, 104nm, 106nm, 108nm, 110nm, 112nm, 114nm, 116nm, 118nm, 120nm, 122nm, 124nm, 126nm, 128nm, 130nm, or any value range between the two.
[0199] In the cross-section along the thickness direction of the positive electrode active material layer, the Dn10 of the lithium transition metal phosphate particles is within a reasonable range, which is beneficial to reduce the specific surface area of the lithium transition metal phosphate particles, reduce the probability of manganese ion dissolution of the lithium transition metal phosphate particles at high temperature, reduce the damage of manganese ions to the SEI film, reduce the consumption of active lithium ions, and improve the cycle stability of the hybrid system battery cell.
[0200] In some embodiments, the electrolyte includes a first component, which includes one or more of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethanesulfonyl)imide.
[0201] In this paper, the types and mass contents of each component in the electrolyte can be obtained by any method known to those skilled in the art. As an example, the composition and content of the electrolyte can be characterized by one or more of the following methods: gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), and gas chromatography-mass spectrometry (GC-MS). For example, referring to GB / T-9722-2023 "General Rules for Gas Chromatography of Chemical Reagents" and / or GB / T6041-2020 "General Rules for Mass Spectrometry Analysis Methods", gas chromatography and mass spectrometry are coupled. After gas chromatography separates the components in the sample, the components are broken into ion fragments in mass spectrometry and separated according to mass-to-charge ratio (m / z) to form specific mass spectra, obtaining qualitative analysis of each organic component in the electrolyte. Then, the organic components in the electrolyte are separated in the chromatographic column, and detection signal spectra of each component are generated. The retention time is used for component qualitative analysis, and the peak area is corrected by standardization to achieve quantification, obtaining quantitative analysis of the organic components in the electrolyte. Referring to JY / T-020, the types of anions of electrolyte salts in the electrolyte are detected by ion chromatography and quantitatively analyzed. Referring to JY / T0578-2020, nuclear magnetic resonance spectroscopy (NMR) is used to obtain qualitative and quantitative analysis of the components in the electrolyte.
[0202] The electrolyte referred to in this article can be either fresh electrolyte or electrolyte obtained from the disassembly of a battery cell. The electrolyte obtained from the disassembly of a battery cell can be either the free electrolyte in the battery casing or the electrolyte obtained by centrifugation from the electrodes.
[0203] In some embodiments, the first component accounts for 0.05%-7% of the total mass of the electrolyte.
[0204] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the first component can be selected as 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%. %, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, or any range of values between the two.
[0205] Because the overall particle size of the lithium transition metal phosphate particles in this embodiment is relatively small, moisture is easily retained inside the battery during the cell manufacturing process. During the cycling process of the battery cell, this moisture easily reacts with conventional lithium-containing electrolyte salts such as lithium hexafluorophosphate in the electrolyte to generate highly corrosive hydrofluoric acid. Hydrofluoric acid easily damages the structure of the lithium transition metal oxide particles, causing transition metal ions to dissolve in the electrolyte and be reduced and precipitated at the negative electrode. Studies have shown that the transition metal deposited on the negative electrode acts as a catalyst, catalyzing the decomposition of the solid electrolyte interphase (SEI) film, causing more active lithium to be consumed during the SEI film repair process, which is detrimental to improving the cycle stability of the hybrid system battery cell.
[0206] The embodiments of this application further incorporate a certain amount of the aforementioned first component, which has excellent thermal stability and is not easily hydrolyzed. It can partially replace the mass ratio of conventional lithium-containing electrolyte salts (such as lithium hexafluorophosphate), which helps to reduce the generation of hydrofluoric acid, reduce the damage of the SEI film to the transition metal ions dissolved from the lithium transition metal oxide particles, reduce the loss of active lithium caused by rebuilding the SEI film, and improve the cycle stability of the hybrid system battery cells.
[0207] In some embodiments, the first component accounts for 0.5%-5% of the total mass of the electrolyte.
[0208] A reasonable mass ratio of the first component in the electrolyte helps to reduce the mass ratio of conventional lithium-containing electrolyte salts (such as lithium hexafluorophosphate), reduce the generation of hydrofluoric acid, reduce its damage to the particle structure of lithium-containing transition metal oxides, and improve the cycle stability of the battery cells in the hybrid system.
[0209] In some embodiments, the first component accounts for 2%-5% of the total mass of the electrolyte.
[0210] A reasonable mass ratio of the first component in the electrolyte helps to further reduce the mass ratio of conventional lithium-containing electrolyte salts (such as lithium hexafluorophosphate), reduce the generation of hydrofluoric acid, reduce its damage to the particle structure of lithium-containing transition metal oxides, and improve the cycle stability of the hybrid system battery cells.
[0211] In some embodiments, the first component includes one or more of lithium bis(fluorosulfonyl)imide and lithium difluorophosphate.
[0212] The first component includes one or more of lithium bis(fluorosulfonyl)imide and lithium difluorophosphate, which helps to reduce the formation of hydrofluoric acid and reduce its damage to the structure of lithium-containing transition metal oxide particles. At the same time, it forms a dense and stable CEI film (positive electrode electrolyte interface film), improves the chemical stability of the CEI film, further blocks the dissolution of transition metal ions in the positive electrode active material, and improves the cycle stability of the hybrid system battery cells.
[0213] In some embodiments, the lithium bis(fluorosulfonyl)imide accounts for 0.05%-2% of the total mass of the electrolyte.
[0214] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide can be selected as 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, or any value range between the two.
[0215] A reasonable mass ratio of lithium difluorosulfonylimide in the electrolyte helps reduce the generation of hydrofluoric acid in the hybrid battery system, reduces the damage of hydrofluoric acid to the structure of lithium-containing transition metal oxide particles, and forms a dense and stable CEI film (positive electrode electrolyte interface film), improving the chemical stability of the CEI film, further blocking the dissolution of transition metal ions in the positive electrode active material, and reducing the probability of excessive corrosion of the current collector due to an excessively high mass ratio of lithium difluorosulfonylimide, thus improving the cycle stability of the hybrid battery cells.
[0216] In some embodiments, the lithium bis(fluorosulfonyl)imide accounts for 0.1%-2% of the total mass of the electrolyte.
[0217] The reasonable mass ratio of lithium difluorosulfonylimide in the electrolyte helps to further reduce the generation of hydrofluoric acid in the hybrid battery system, reduce the damage of hydrofluoric acid to the particle structure of lithium-containing transition metal oxides, and form a dense and stable CEI film (positive electrode electrolyte interface film), improve the chemical stability of the CEI film, further block the dissolution of transition metal ions in the positive electrode active material, and improve the cycle stability of the hybrid battery cells.
[0218] In some embodiments, the lithium difluorophosphate accounts for 1%-5% of the total mass of the electrolyte.
[0219] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate can be selected as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, or any value range between the two.
[0220] A reasonable mass ratio of lithium difluorophosphate in the electrolyte helps reduce the generation of hydrofluoric acid in the hybrid battery system, reduces the damage of hydrofluoric acid to the structure of lithium-containing transition metal oxide particles, and forms a dense and stable CEI film (positive electrode electrolyte interface film), improving the chemical stability of the CEI film, further blocking the dissolution of transition metal ions in the positive electrode active material, and reducing the probability of excessively high film-forming impedance due to an excessively high mass ratio of lithium difluorophosphate, thereby improving the cycle stability of the hybrid battery cells.
[0221] In some embodiments, the lithium difluorophosphate accounts for 2%-5% of the total mass of the electrolyte.
[0222] A reasonable mass ratio of lithium difluorophosphate in the electrolyte helps to further reduce the generation of hydrofluoric acid in the hybrid battery system, reduce the damage of hydrofluoric acid to the structure of lithium-containing transition metal oxide particles, and form a dense and stable CEI film (positive electrode electrolyte interface film), improve the chemical stability of the CEI film, further block the dissolution of transition metal ions in the positive electrode active material, and improve the cycle stability of the hybrid battery cell.
[0223] In some embodiments, the electrolyte comprises lithium hexafluorophosphate, and the mass percentage of lithium hexafluorophosphate is 5%-12% based on the total mass of the electrolyte.
[0224] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium hexafluorophosphate can be selected as 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10%, 10.5%, 11%, 11.5%, 12%, or any value range between the two.
[0225] Although lithium hexafluorophosphate hydrolyzes to produce hydrofluoric acid, it has high solubility and ionic conductivity in the electrolyte, which is beneficial for increasing the lithium-ion content in the electrolyte. At the same time, when the mass ratio of lithium hexafluorophosphate in the electrolyte is within a reasonable range, it is beneficial to improve the ionic conductivity of the electrolyte while reducing the amount of hydrofluoric acid generated, reducing the damage to the structure of lithium-containing transition metal oxide particles, and further improving the cycle performance of the hybrid system battery cells.
[0226] In some embodiments, the electrolyte includes a second component, which includes one or more of 1,3-propanesulfonyl lactone, lithium difluorooxalate borate, trimethylsilyl phosphate, lithium bis(oxalate borate), and vinyl sulfate; optionally, the second component includes 1,3-propanesulfonyl lactone.
[0227] The inclusion of a second component in the electrolyte is beneficial for forming a dense and stable SEI film, improving the chemical stability of the SEI film, reducing the damage of the SEI film by transition metal ions, reducing the loss of active lithium caused by rebuilding the SEI film, and improving the cycle stability of the hybrid system battery cells.
[0228] In some embodiments, the second component accounts for 0.2%-5% of the total mass of the electrolyte.
[0229] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the second component can be selected as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, or any value range between the two.
[0230] When the mass ratio of the second component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film, improve the chemical stability of the SEI film, reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time reduce the probability of excessive film resistance caused by an excessively high mass ratio of the second component, thereby improving the cycle stability of the hybrid system battery cells.
[0231] In some embodiments, the second component accounts for 0.5%-3% of the total mass of the electrolyte.
[0232] When the mass ratio of the second component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film, improve the chemical stability of the SEI film, further reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and improve the cycle stability of the battery cells in the hybrid system.
[0233] In some embodiments, the second component accounts for 0.5%-1% of the total mass of the electrolyte.
[0234] When the mass ratio of the second component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film, improve the chemical stability of the SEI film, further reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time take into account the interfacial impedance of the film formation, thus improving the cycle stability of the battery cells in the hybrid system.
[0235] In some embodiments, the electrolyte comprises cyclic carbonate compounds, and the cyclic carbonate compounds account for 20%-45% of the total mass of the electrolyte.
[0236] In this application, cyclic carbonate compounds refer to cyclic compounds whose molecular structure contains carbonate functional groups (–O–C(=O)–O–).
[0237] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the cyclic carbonate compound can be selected as 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or any value range between the two.
[0238] The electrolyte contains a certain amount of cyclic carbonate compounds, which have a high dielectric constant. This is beneficial for improving the degree of lithium salt dissociation and ionic conductivity in the electrolyte, making it easier for lithium ions in the electrolyte to diffuse, reducing the probability of local lithium plating in the mixed system, and improving the cycle stability of the battery cells in the mixed system.
[0239] In some embodiments, the electrolyte comprises cyclic carbonate compounds, and the cyclic carbonate compounds account for 18%-35% of the total mass of the electrolyte.
[0240] A reasonable mass ratio of cyclic carbonate compounds in the electrolyte is beneficial for improving the degree of lithium salt dissociation and ionic conductivity in the electrolyte, making it easier for lithium ions to diffuse in the electrolyte, reducing the probability of local lithium plating in the mixed system, and improving the cycle stability of the battery cells in the mixed system.
[0241] In some embodiments, the cyclic carbonate compound includes one or more of ethylene carbonate, propylene carbonate, and butene carbonate; optionally, the cyclic carbonate compound includes ethylene carbonate.
[0242] In some embodiments, the electrolyte comprises chain carbonate compounds, and the chain carbonate compounds account for 40%-75% of the total mass of the electrolyte.
[0243] In this application, chain carbonate compounds refer to chain compounds whose molecular structure contains carbonate functional groups (–O–C(=O)–O–).
[0244] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the chain carbonate compound can be selected as 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, or any value range between the two.
[0245] The electrolyte contains a certain amount of chain carbonate compounds, which have low viscosity. This helps to improve the electrolyte's wetting ability on the electrode and the lithium-ion transport rate, reduce the probability of localized excessive lithium-ion concentration and uneven lithium salt distribution in the hybrid battery system, and improve the cycle stability of the hybrid battery cells.
[0246] In some embodiments, the electrolyte comprises chain carbonate compounds, and the chain carbonate compounds account for 50%-70% of the total mass of the electrolyte.
[0247] A reasonable mass ratio of chain carbonate compounds in the electrolyte is beneficial for improving the electrolyte's wetting ability on the electrode and the lithium-ion transport rate, reducing the probability of excessively high local lithium-ion concentration and uneven lithium salt distribution in the hybrid battery system, and improving the cycle stability of the hybrid battery cells.
[0248] In some embodiments, the chain carbonate compound includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methyl propyl carbonate; optionally, the chain carbonate includes ethyl methyl carbonate and diethyl carbonate.
[0249] In some embodiments, the electrolyte comprises ethyl methyl carbonate, and the ethyl methyl carbonate accounts for 35%-55% of the total mass of the electrolyte.
[0250] In some embodiments, based on the total mass of the electrolyte, the mass percentage of methyl ethyl carbonate can be selected as 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, 55%, or any value range between the two.
[0251] The electrolyte contains an appropriate amount of ethyl methyl carbonate, which has high stability and low viscosity. It can be adapted to the high-voltage environment of the hybrid battery cell, which is beneficial to improving the electrolyte's wetting ability on the electrode and the lithium-ion transport rate. It also reduces the probability of localized excessive lithium-ion concentration and uneven lithium salt distribution in the hybrid battery, and improves the cycle stability of the hybrid battery cell.
[0252] In some embodiments, the electrolyte includes diethyl carbonate, and the mass percentage of diethyl carbonate is 10%-20% based on the total mass of the electrolyte.
[0253] In some embodiments, based on the total mass of the electrolyte, the mass percentage of diethyl carbonate can be selected as 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, or any value range between the two.
[0254] The electrolyte contains an appropriate amount of diethyl carbonate, which has high stability and low viscosity. It can be adapted to the high-voltage environment of the hybrid battery cell, which is beneficial to improving the electrolyte's wetting ability on the electrode and the lithium-ion transport rate. It also reduces the probability of localized excessive lithium-ion concentration and uneven lithium salt distribution in the hybrid battery, and improves the cycle stability of the hybrid battery cell.
[0255] In some embodiments, the electrolyte includes a third component, which includes one or more of vinylene carbonate and fluoroethylene carbonate.
[0256] The electrolyte includes a third component that can form a dense and stable SEI film at the negative electrode, which helps to reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and improve the cycle stability of the hybrid system battery cells.
[0257] In some embodiments, the third component accounts for 0.08%-5% of the total mass of the electrolyte.
[0258] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the third component can be selected as 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.48%, 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, 0.62%, 0.64%, 0.66%, 0.68%, 0.7%, 0.72%, 0.74%, 0.76%, 0.78%, 0.8%, 0.82%. %, 0.84%, 0.86%, 0.88%, 0.9%, 0.92%, 0.94%, 0.96%, 0.98%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, or any range between the two.
[0259] When the mass proportion of the third component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film on the negative electrode, which helps to reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time reduce the probability of excessive film-forming impedance caused by an excessively high mass proportion of the third component, thereby improving the cycle stability of the hybrid system battery cells.
[0260] In some embodiments, the third component accounts for 0.5%-3% of the total mass of the electrolyte.
[0261] When the mass proportion of the third component in the electrolyte is within a reasonable range, it is beneficial to form a dense and stable SEI film on the negative electrode, which helps to reduce the damage of the SEI film by transition metal ions, reduce the loss of active lithium caused by rebuilding the SEI film, and at the same time reduce the probability of excessive film-forming impedance caused by an excessively high mass proportion of the third component, thereby improving the cycle stability of the hybrid system battery cells.
[0262] In some embodiments, the Dn50 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 1μm-4μm.
[0263] In this application, the Dn10, Dn50, and Dn90 of lithium transition metal oxide particles in the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet can be specifically tested using the following method: Disassemble the battery to obtain the positive electrode sheet. After distinguishing between lithium transition metal oxide particles and lithium transition metal oxide particles in the cross-section of the positive electrode active material layer along the thickness direction according to the above method, locate the region containing lithium transition metal oxide particles. Use ImageJ software (1.46r, win64 version) to analyze the lithium transition metal oxide particles in the electron microscope image. The specific method for using ImageJ software is as follows: Load the scanning electron microscope image to be analyzed; use the Cellpose plugin software to identify the particles, and then manually correct or label the lithium transition metal oxide particles; finally, use ImageJ to read and analyze the data.
[0264] The specific method for identifying particles using the Cellpose plugin software is as follows: Set the segmentation diameter parameter (diameter in the Segmentation module) to 15 pixels, click "runcyto3" to perform particle identification; manually mark the particles in the image that were not identified by the software, were not fully identified by the software, or had identification errors. The particles that were not identified by the software, were not fully identified by the software, or had identification errors mainly include the following: 1. Particles that are too large or have scratches on their surface, making them unidentifiable or incompletely identifiable; 2. During argon ion beam cutting, scratches may be generated on the particle surface, and the software may misjudge these scratches as particle boundaries during identification, leading to identification errors; 3. Particles that are too small and were not successfully identified; 4. Particles located at the edge of the electron microscope field of view, with the particle's interior penetrated by the edge, preventing a complete display of the morphology, and resulting in identification errors due to partial identification replacing the whole. For the unidentified or misidentified particles mentioned above, manual calibration is performed. The specific process is as follows: 1. Delete large particles located around the edges of the scanning electron microscope that are not fully displayed. 2. Determine if any unidentified or misidentified particles have internal cracks or scratches. If no cracks or scratches are found, classify it as a single particle and manually mark it based on the observed particle boundary. 3. If cracks or scratches are found inside the particle, determine if they penetrate the particle. If not, classify it as a single particle and manually mark it. 4. If cracks or scratches penetrate the particle, determine if they are linear or irregular. 5. If the cracks or scratches are irregular, classify them as the boundary between particles and divide the particles along this boundary. 6. If the cracks or scratches are linear, perform contrast comparison. 7. If the contrast is not obvious and there is no crack-like appearance, classify it as a scratch and mark it as a single particle. 8. If the contrast is strong and there is a crack-like appearance, classify it as the boundary between particles and mark it as two particles. After manual marking, delete information irrelevant to the particles from the automatic image processing, thus completing the particle identification and marking in the image.
[0265] The "Feret" parameter of lithium-containing transition metal oxide particles obtained from statistical analysis is used as the particle size. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter obtained from the analysis represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. Since particles with a diameter less than 50 nm have a large error in the statistical process and are difficult to accurately identify, and the particle size of conductive agents is generally less than 50 nm, which will also introduce a large error into the statistical results, particles with a diameter less than 50 nm are not counted in the particle size statistics of this application. Following the above method, to ensure a statistically significant sample size, at least 10 non-overlapping scanning electron microscope images were acquired for each electrode. The particle size of at least 100 lithium transition metal oxide particles was statistically analyzed. After obtaining all the measurement data, they were arranged in ascending order. The value at the median position was taken as the particle size Dn50 of the lithium transition metal oxide particles, meaning that 50% of the particles have a particle size no larger than this value and 50% of the particles have a particle size no smaller than this value. The value at the 90% cumulative position was taken as the particle size Dn90 of the lithium transition metal oxide particles, meaning that 90% of the particles have a particle size no larger than this value. The value at the 10% cumulative position was taken as the particle size Dn10 of the lithium transition metal oxide particles, meaning that 10% of the particles have a particle size no larger than this value.
[0266] In some embodiments, the Dn50 of the lithium-containing transition metal oxide particles in the cross-section along the thickness direction of the positive electrode active material layer can be selected as 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, or any value range between the two.
[0267] In hybrid battery cells, the negative electrode location corresponding to lithium transition metal oxide particles is prone to local lithium plating. This is because, compared to lithium transition metal phosphate particles, the region containing lithium transition metal oxide materials releases a large number of lithium ions per unit time, requiring the corresponding negative electrode side to bear a high concentration of lithium ion insertion, and even triggering local lithium plating. In this embodiment, by controlling the Dn50 of the lithium transition metal oxide particles within the above-mentioned range, it means that the particle size of the lithium transition metal oxide particles is smaller, which is beneficial to improving the uniformity of the distribution of lithium transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid battery cell.
[0268] In some embodiments, the Dn50 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 1μm-3μm.
[0269] Within a reasonable range, the Dn50 of lithium-containing transition metal oxide particles is beneficial to further improve the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0270] In some embodiments, the Dn50 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 1.5 μm-2.5 μm.
[0271] Within a reasonable range, the Dn50 of lithium-containing transition metal oxide particles is beneficial to further improve the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0272] In some embodiments, the particle size distribution concentration (Dn90-Dn10) / Dn50 of the lithium-containing transition metal oxide particles in the cross section along the thickness direction of the positive electrode active material layer is 0.6-2.
[0273] In some embodiments, the particle size distribution concentration (Dn90-Dn10) / Dn50 of the lithium-containing transition metal oxide particles in the cross-section along the electrode thickness direction of the positive electrode active material layer can be selected as 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1, 1.02, 1.04, 1.06, 1.08, 1.1, 1.12, 1.14, 1.16, 1 18, 1.2, 1.22, 1.24, 1.26, 1.28, 1.3, 1.32, 1.34, 1.36, 1.38, 1.4, 1.42, 1.44, 1.46, 1.48, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.62, 1.64, 1.66, 1.68, 1.7, 1.72, 1.74, 1.76, 1.78, 1.8, 1.82, 1.84, 1.86, 1.88, 1.9, 1.92, 1.94, 1.96, 1.98, 2, or any range of values between two of these.
[0274] The particle size distribution concentration of lithium-containing transition metal oxide particles is within a suitable range, indicating that the particle size is highly consistent. This reduces the specific capacity difference in different regions of the positive electrode active material layer, thereby reducing the phenomenon of local lithium-ion concentration concentration, alleviating local lithium plating, and further improving the cycle stability of the hybrid system battery cell.
[0275] In some embodiments, the particle size distribution concentration (Dn90-Dn10) / Dn50 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 0.8-1.8.
[0276] The particle size distribution concentration of lithium-containing transition metal oxide particles is within a suitable range, which is beneficial to further reduce the difference in specific capacity in different regions of the positive electrode active material layer, thereby reducing the phenomenon of local lithium-ion concentration concentration, alleviating local lithium plating, and further improving the cycle stability of the hybrid system battery cell.
[0277] In some embodiments, the Dn10 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 0.5 μm-2 μm.
[0278] In some embodiments, the Dn10 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction can be selected as 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm or any value range between the two.
[0279] The Dn10 of lithium-containing transition metal oxide particles within the above range is beneficial to reducing the particle size of lithium-containing transition metal oxide particles, improving the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0280] In some embodiments, the Dn10 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 0.5 μm-1.5 μm.
[0281] When the Dn10 of lithium-containing transition metal oxide particles is within a suitable range, it is beneficial to reduce the particle size of lithium-containing transition metal oxide particles, improve the uniformity of distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0282] In some embodiments, the Dn90 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 2.5 μm-5 μm.
[0283] In some embodiments, the Dn90 of the lithium-containing transition metal oxide particles in the cross-section along the thickness direction of the positive electrode active material layer can be selected as 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5μm, or any value range between the two.
[0284] The Dn90 of lithium-containing transition metal oxide particles within the above range is beneficial to reducing the particle size of lithium-containing transition metal oxide particles, improving the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0285] In some embodiments, the Dn90 of the lithium-containing transition metal oxide particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 3μm-4μm.
[0286] The Dn90 of lithium-containing transition metal oxide particles within the above range is beneficial to reducing the particle size of lithium-containing transition metal oxide particles, improving the uniformity of the distribution of lithium-containing transition metal oxide materials in the positive electrode active material layer, thereby reducing the local lithium-ion concentration, alleviating the local lithium plating phenomenon, and further improving the cycle stability of the hybrid system battery cell.
[0287] In some embodiments, the percentage of nickel moles is 50%-80% based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles.
[0288] Based on the total molar number of nickel, cobalt, and M elements in the lithium-containing transition metal oxide particles, the molar percentage of nickel can be tested using methods and equipment known in the art. A specific test method is illustrated below: Disassemble the battery cell to obtain the positive electrode sheet. Cut the positive electrode sheet into 6mm × 6mm samples using ceramic scissors and attach them to a sample stage coated with paraffin wax, ensuring the sample protrudes slightly (<1mm) from the edge of the sample stage. Then, turn on the power of the argon ion cross-section polisher (JEOL IB-09010 CP type argon ion cross-section polisher from Japan) and apply a vacuum (10⁻⁷ Pa). Adjust the parameters, and then use the polisher to cut the positive electrode test film layer along the thickness direction of the sample. After exposing the cut surface, use a scanning electron microscope to observe the cross-section of the positive electrode sheet along the thickness direction. Observe the positive current collector and the positive active material layers on both sides of the positive current collector under the scanning electron microscope. Then, adjust the field of view to the positive active material layer, and use the field of view area as the test area. Electron microscopy (SEM) images were taken to obtain scanning electron microscope (SEM) images of the cross-section of the positive electrode active material layer along the thickness direction of the positive electrode sheet. Energy dispersive spectroscopy (EDS) was performed on the test area. Based on the distribution spectrum of phosphorus (P) in the test area, the area where P was not clearly visible was magnified, and the particle composition was determined by EDS, identifying it as lithium-containing transition metal oxide (LMO) particles. Selected LEM particles were subjected to EDS testing to obtain the molar percentage of each element in the particles. This was then converted to calculate the molar percentage of nickel based on the total molar number of nickel, cobalt, and methyl (M) elements in the LEM particles. At least 100 particles were measured, and the average value was taken as the test result.
[0289] In some embodiments, based on the total molar number of nickel, cobalt, and M elements in the lithium-containing transition metal oxide particles, the molar percentage of nickel can be selected as 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, or any value range between the two.
[0290] Increasing the nickel content in lithium-containing transition metal oxide particles helps to increase specific capacity while lowering the upper limit of its operating voltage. In the embodiments of this application, the nickel content in the lithium-containing transition metal oxide particles within the above-mentioned range helps to reduce the charging cut-off voltage of the hybrid system battery cell, reduce the voltage range difference between lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles, alleviate load shunting phenomenon, and improve the cycle stability of the hybrid system battery cell.
[0291] In some embodiments, the molar percentage of cobalt is 5%-20%, based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles.
[0292] Based on the total molar number of nickel, cobalt, and M elements in the lithium-containing transition metal oxide particles, the molar percentage of cobalt can be obtained by referring to the molar percentage test of nickel mentioned above.
[0293] In some embodiments, based on the total molar number of nickel, cobalt, and M elements in the lithium-containing transition metal oxide particles, the molar percentage of cobalt can be selected as 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, or any value range between the two.
[0294] Cobalt can enhance the order and stability of the lattice of lithium-containing transition metal oxide particles. Based on the total molar number of nickel, cobalt and M elements in lithium-containing transition metal oxide particles, the molar proportion of cobalt within the above range is beneficial to improving the stability of lithium-containing transition metal oxide particles and improving the cycle stability of hybrid battery cells.
[0295] In some embodiments, the molar percentage of element M is 15%-40% based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles.
[0296] Based on the total number of moles of nickel, cobalt, and M in the lithium-containing transition metal oxide particles, the molar percentage of M can be obtained by referring to the molar percentage test of nickel mentioned above.
[0297] In some embodiments, based on the total molar number of nickel, cobalt, and M elements in the lithium-containing transition metal oxide particles, the molar percentage of the M element can be selected as 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, or any value range between the two.
[0298] In some embodiments, the lithium-containing transition metal oxide particles are single-crystal particles.
[0299] The lithium-containing transition metal oxide particles are single-crystal particles, meaning that their overall crystal is continuous and there are no grain boundary structures inside. This can effectively reduce stress concentration during charging and discharging and inhibit particle cracking, thereby improving the cycle stability of the hybrid battery cell.
[0300] In some embodiments, the lithium-containing transition metal oxide particles account for 50%-90% of the total mass of the positive electrode active material.
[0301] In this application, the "mass percentage of lithium transition metal oxide particles based on the total mass of the positive electrode active material" can be obtained by any method known in the art. For example, inductively coupled plasma atomic emission spectrometry (ICP) or X-ray diffraction (XRD) can be used for detection. Taking ICP as an example, the battery cell is disassembled to obtain the positive electrode sheet, and the positive electrode active material powder is obtained by scraping. The powder is then completely digested with acid (such as HNO3-HCl mixed acid) under isothermal conditions, so that all Ni, Co, M (Mn and / or Al), Fe, and P elements in the sample enter the solution. The elemental concentrations of Ni, Co, M, Fe, and P elements in the solution are measured by inductively coupled plasma atomic emission spectrometry (ICP-OES) or inductively coupled plasma mass spectrometry (ICP-MS). The mass of lithium transition metal oxide particles is calculated based on the molar ratio of Ni, Co, and M elements and the molar mass of each element in the lithium transition metal oxide particles. Then, the mass of lithium transition metal phosphate particles is calculated by combining the Fe and P elements. The mass percentage of lithium transition metal oxide particles is obtained based on the total mass of both.
[0302] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the lithium transition metal oxide particles can be selected as 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, or any value range between the two.
[0303] Having the mass percentage of lithium transition metal oxide particles within the above range is beneficial for improving the energy density of hybrid battery cells while taking into account the manufacturing cost of hybrid battery cells.
[0304] In some embodiments, the lithium-containing transition metal oxide particles account for 60%-80% of the total mass of the positive electrode active material.
[0305] A reasonable mass ratio of lithium transition metal oxide particles is beneficial for further improving the energy density of hybrid battery cells while taking into account the manufacturing cost of hybrid battery cells.
[0306] In some embodiments, the lithium-containing transition metal oxide particles include one or more of lithium-containing nickel-cobalt-manganese oxide particles and their doped and / or coated modified materials, and lithium-containing nickel-cobalt-aluminum oxide particles and their doped and / or coated modified materials.
[0307] In some embodiments, the lithium-containing transition metal phosphate particles include a particle body and a carbon material disposed on at least a portion of the surface of the particle body.
[0308] In some embodiments, the thickness of the carbon material is 2nm-25nm.
[0309] In this application, the thickness of the carbon material on the surface of lithium transition metal phosphate particles can be tested using methods and instruments known in the art. As an example, a cross-section along the thickness direction of the positive electrode active material layer is obtained using the method described above. The lithium transition metal phosphate particles in the cross-section are then observed using a transmission electron microscope (TEM), and the particle composition is confirmed by energy dispersive spectroscopy (EDS). The continuously distributed carbon material on the particle surface can be identified in the TEM image. This image is imported into ImageJ software, and the thickness of the carbon material is measured along the radial direction of the particles. Measurements are performed on at least 50 particles, and the average value is taken as the characterization result of the carbon material thickness.
[0310] In some embodiments, the thickness of the carbon material can be selected as 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm, 10.5nm, 11nm, 11.5nm, 12nm, 12.5nm, 13nm, 13.5nm, 14nm, 14.5nm, 15nm, 15.5nm, 16nm, 16.5nm, 17nm, 17.5nm, 18nm, 18.5nm, 19nm, 19.5nm, 20nm, 20.5nm, 21nm, 21.5nm, 22nm, 22.5nm, 23nm, 23.5nm, 24nm, 24.5nm, 25nm, or any value range between the two.
[0311] Within the aforementioned range, the thickness of the carbon material on the surface of lithium transition metal phosphate particles is beneficial for improving the electronic conductivity of lithium transition metal phosphate particles, enhancing their kinetic performance, reducing the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reducing the probability of lithium transition metal oxide particles breaking and surface structure collapsing due to current overload, and improving the cycle stability of the hybrid battery cell.
[0312] In some embodiments, the carbon material accounts for 0.5%-3% of the total mass of the lithium transition metal phosphate particles.
[0313] In this application, the types and contents of elements in lithium transition metal phosphate particles can be tested using any method known in the art. As an example, inductively coupled plasma atomic emission spectrometry (ICP-AES) is used to test the carbon content, referring to Appendix C of GB / T 33822-2017.
[0314] In some embodiments, based on the total mass of the lithium transition metal phosphate particles, the mass percentage of the carbon material can be selected as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, or any value range between the two.
[0315] When the mass percentage of carbon in lithium transition metal phosphate particles is within the above range, it is beneficial to improve the electronic conductivity of lithium transition metal phosphate particles, improve their kinetic performance, reduce the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reduce the probability of lithium transition metal oxide particles breaking and surface structure collapse due to current overload, and improve the cycle stability of the hybrid battery cell.
[0316] In some embodiments, the lithium-containing transition metal phosphate particles comprise the components represented by the following general formula I: Li m1 Fe x1 Mn y1 M1 b1 P z1 Q1 c1 O n1 N1 d1 Formula I; Wherein, 0.8≤m1≤1.2, 0<x1<1, 0<y1<1, 0.9≤x1+y1≤1, 0.95≤z1≤1, 3.5≤n1≤4, 0≤b1≤0.1, 0≤c1≤0.1, 0≤d1≤0.1; wherein, M1 includes one or more of Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, and Ti, Q1 includes one or more of B, S, Si, and N, and N1 includes one or more of F, Cl, and Br.
[0317] In some implementations, m1 can be selected as 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.2, or any value range between the two.
[0318] In some implementations, x1 can be selected as 0.01, 0.04, 0.07, 0.1, 0.13, 0.16, 0.19, 0.22, 0.25, 0.28, 0.31, 0.34, 0.37, 0.4, 0.43, 0.46, 0.49, 0.52, 0.55, 0.58, 0.61, 0.64, 0.67, 0.7, 0.73, 0.76, 0.79, 0.82, 0.85, 0.88, 0.91, 0.94, 0.97, 0.98, 0.99, or any value range between the two.
[0319] In some implementations, y1 can be selected as 0.01, 0.04, 0.07, 0.1, 0.13, 0.16, 0.19, 0.22, 0.25, 0.28, 0.31, 0.34, 0.37, 0.4, 0.43, 0.46, 0.49, 0.52, 0.55, 0.58, 0.61, 0.64, 0.67, 0.7, 0.73, 0.76, 0.79, 0.82, 0.85, 0.88, 0.91, 0.94, 0.97, 0.98, 0.9, or any value range between the two.
[0320] In some implementations, x1+y1 can be selected as 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, or any range between the two.
[0321] In some implementations, z1 can be selected as 0.95, 0.96, 0.97, 0.98, 0.99, 1, or any value range between the two.
[0322] In some implementations, n1 can be selected as 3.5, 3.51, 3.52, 3.53, 3.54, 3.55, 3.56, 3.57, 3.58, 3.59, 3.6, 3.61, 3.62, 3.63, 3.64, 3.65, 3.66, 3.67, 3.68, 3.69, 3.7, 3.71, 3.72, 3.73, 3.74, 3.75, 3.76, 3.77, 3.78, 3.79, 3.8, 3.81, 3.82, 3.83, 3.84, 3.85, 3.86, 3.87, 3.88, 3.89, 3.9, 3.91, 3.92, 3.93, 3.94, 3.95, 3.96, 3.97, 3.98, 3.99, 4, or any range of two.
[0323] In some implementations, b1 can be selected as 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or any value range between the two.
[0324] In some implementations, c1 can be selected as 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or any value range between the two.
[0325] In some implementations, d1 can be selected as 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value range between the two.
[0326] Selecting appropriate modifying elements can improve the ion diffusion pathway of lithium-containing transition metal phosphate particles, increase the lithium-ion diffusion rate of lithium-containing transition metal phosphate particles, reduce the degree of kinetic performance mismatch between the two types of materials in the hybrid battery cell, reduce the probability of lithium-containing transition metal oxide particles breaking and surface structure collapse due to current overload, and improve the cycle stability of the hybrid battery cell.
[0327] In some embodiments, the positive electrode active material layer includes a first conductive agent, which includes a dotted conductive agent, and the dotted conductive agent includes one or more of Super P, Ketjen Black, acetylene black, and conductive graphite.
[0328] In some embodiments, the mass percentage of the dot-shaped conductive agent is 0.2%-2.0% based on the total mass of the positive electrode active material layer.
[0329] In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the dotted conductive agent can be selected as 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45%, 1.5%, 1.55%, 1.6%, 1.65%, 1.7%, 1.75%, 1.8%, 1.85%, 1.9%, 1.95%, 2%, or any value range between the two.
[0330] In some embodiments, the first conductive agent further includes a linear conductive agent, which includes one or more of carbon nanotubes, vapor-grown carbon fibers, and carbon nanofibers; optionally, the first conductive agent includes carbon nanotubes.
[0331] The combined use of dot-like and linear conductive agents balances both long-range and short-range conductivity, which is beneficial for further improving the conductive network in the positive electrode active material layer.
[0332] In some embodiments, the mass percentage of the linear conductive agent is 0.05%-1.5% based on the total mass of the positive electrode active material layer.
[0333] In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the linear conductive agent can be selected as 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.25%, 1.5%, or any value range between the two.
[0334] In some embodiments, the linear conductive agent accounts for 0.05%-1.25% of the total mass of the positive electrode active material layer.
[0335] In some embodiments, the positive electrode includes a positive electrode film layer disposed on at least one side of the positive electrode current collector, the positive electrode film layer including the positive electrode active material layer and a positive electrode undercoating layer disposed between the positive electrode active material layer and the positive electrode current collector; the positive electrode undercoating layer includes a first polymer and a second conductive agent.
[0336] In some embodiments, the first polymer includes a vinylidene fluoride polymer, which includes one or more of vinylidene fluoride homopolymers, copolymers of vinylidene fluoride and tetrafluoroethylene, copolymers of vinylidene fluoride and hexafluoropropylene, and copolymers of vinylidene fluoride and trifluoroethylene.
[0337] In some embodiments, the second conductive agent includes one or more of Super P, Ketjen Black, acetylene black, conductive graphite, and carbon nanotubes.
[0338] In some embodiments, the thickness of the positive electrode undercoat is 0.5 μm-5 μm.
[0339] In some embodiments, the thickness of the positive electrode undercoat can be selected as 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, or 2.6μm. 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5μm or any range between the two.
[0340] In some embodiments, the compaction density of the positive electrode film is 2.60 g / cm³. 3 -3.4g / cm 3 .
[0341] In this paper, the compaction density of the positive electrode film can be tested using methods known in the art. As an example, the battery cell is placed at 25°C and discharged at a constant current of 0.05C to 2.0V. The fully discharged electrode is then disassembled, and residual electrolyte is cleaned using an organic solvent (the organic solvent can be any solvent commonly used in the art capable of cleaning electrolytes, including but not limited to dimethyl carbonate). After removing the residual electrolyte, the electrode is dried, and a test sample of electrode area S is weighed using an electronic balance, with the weight recorded as W. The thickness T of the positive electrode film is then measured (for example, by cutting the positive electrode with an ion beam and then observing the cross-section of the positive electrode film using a scanning electron microscope to obtain the thickness of the positive electrode film). The compaction density of the positive electrode film can be calculated using the formula W / (T×S), with units of g / cm³. 3 .
[0342] In some embodiments, the compaction density of the positive electrode film can be selected as 2.6 g / cm³. 3 2.65g / cm 3 2.7g / cm 3 2.75g / cm 3 2.8g / cm 3 2.85g / cm3 2.9g / cm 3 2.95g / cm 3 3g / cm 3 3.05g / cm 3 3.1g / cm 3 3.15g / cm 3 3.2g / cm 3 3.25g / cm 3 3.3g / cm 3 3.35g / cm 3 3.4g / cm 3 Or the range of values between any two.
[0343] Within the aforementioned range, the compaction density of the cathode film ensures a high packing density of the active material, achieving a high volumetric energy density, while maintaining a suitable pore structure, which is beneficial for electrolyte wetting and lithium-ion transport. This achieves both high energy density and improved kinetic performance of the cathode film.
[0344] In some embodiments, the electrode assembly includes a negative electrode sheet, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector, the negative active material layer includes a negative active material, the negative active material includes graphite, and the volume distribution particle size Dv50 of the negative active material is 7μm-15μm.
[0345] In this application, Dv50 has a well-known meaning in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 50%, which can be determined using instruments and methods known in the art. For example, it can be conveniently determined using a laser particle size analyzer, referring to GB / T19077-2016 Particle Size Distribution Laser Diffraction Method. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0346] It is worth noting that the negative electrode active material layer and the negative electrode active material used for testing in this application can be freshly prepared or obtained by disassembling, washing, drying (and scraping powder) from the battery.
[0347] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material can be selected as 7 μm, 7.2 μm, 7.4 μm, 7.6 μm, 7.8 μm, 8 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm, 10 μm, 10.2 μm, 10.4 μm, 10.6 μm, 10.8 μm, 11μm, 11.2μm, 11.4μm, 11.6μm, 11.8μm, 12μm, 12.2μm, 12.4μm, 12.6μm, 12.8μm, 13μm, 13.2μm, 13.4μm, 13.6μm, 13.8μm, 14μm, 14.2μm, 14.4μm, 14.6μm, 14.8μm, 15μm, or any range of two.
[0348] In the embodiments of this application, controlling the volume distribution particle size Dv50 of graphite in the negative electrode active material within a suitable range is beneficial to increasing the lithium-ion insertion port, shortening the lithium-ion diffusion path, thereby improving the lithium-ion insertion rate, reducing local lithium plating, and improving the cycle stability of the hybrid system battery cell.
[0349] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 8 μm-13 μm.
[0350] In the embodiments of this application, controlling the volume distribution particle size Dv50 of graphite in the negative electrode active material within a suitable range is beneficial to increasing the lithium-ion insertion port and shortening the lithium-ion diffusion path, thereby improving the lithium-ion insertion rate and reducing local lithium plating. At the same time, controlling the specific surface area of graphite reduces the probability of exacerbating electrolyte side reactions due to excessive specific surface area of graphite, and improves the cycle stability of the hybrid system battery cell.
[0351] In some embodiments, the electrode assembly further includes a separator disposed on at least one side of the positive electrode sheet. The separator includes a base film, a first coating disposed on both sides of the base film, and a second coating disposed between the first coating and the base film. Optionally, the second coating is disposed near the positive electrode sheet. The first coating includes a second polymer, and the second coating includes inorganic particles and a third polymer.
[0352] The first coating comprises a polymer with good adhesion, which helps to improve the adhesion of the separator. The second coating is further disposed on the side of the base film close to the positive electrode, which helps to reduce the direct contact between the base film and the positive electrode active material, reduce the damage to the base film caused by byproducts generated by the electrolyte at the positive electrode active material, thereby improving the stability of the separator and further improving the cycle stability of the hybrid battery cell.
[0353] In some embodiments, the second polymer and the third polymer each independently include one or more of fluoropolymers and acrylate polymers.
[0354] In some embodiments, the fluoropolymer includes a vinylidene fluoride polymer, which includes one or more of vinylidene fluoride homopolymers, copolymers of vinylidene fluoride and tetrafluoroethylene, copolymers of vinylidene fluoride and hexafluoropropylene, and copolymers of vinylidene fluoride and trifluoroethylene.
[0355] In some embodiments, the acrylate polymer includes acrylate-acrylonitrile-acrylamide-propylene copolymers.
[0356] In some embodiments, the inorganic particles include one or more of alumina, boehmite, silicon dioxide, cerium oxide, magnesium aluminate, zirconium oxide, and titanium dioxide.
[0357] In some embodiments, the rated cutoff voltage of the battery cell is 4.25V-4.45V.
[0358] In this application, the rated cutoff voltage of a battery cell refers to the charging cutoff voltage of the battery cell, that is, the highest voltage that the battery cell is allowed to reach during charging. The rated cutoff voltage of a battery cell can be obtained in the following ways: for example, from the nameplate of the battery device, power consumption device, or energy storage device; from the charging cutoff voltage of the corresponding positive electrode active material described in the literature; or it can be determined by performing a standard charging test on the battery cell and recording the charging curve. As an example, when charging a battery cell using the rated current, the voltage corresponding to the highest charging plateau in the charging curve is taken as the rated cutoff voltage of the battery cell.
[0359] In some embodiments, the rated cutoff voltage of the battery cell can be selected as 4.25V, 4.3V, 4.31V, 4.32V, 4.33V, 4.34V, 4.35V, 4.36V, 4.37V, 4.38V, 4.39V, 4.4V, 4.41V, 4.42V, 4.43V, 4.44V, 4.45V, or any value range between the two.
[0360] In some embodiments, the housing further includes an end cap, and the ratio of the size of the first portion to the size of the end cap is 0.35-0.80 along the thickness direction of the battery cell.
[0361] In some embodiments, the ratio of the size of the first portion to the size of the end cap along the thickness direction of the battery cell can be selected as 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, or 0.5. 4. 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, or any value range between two of these.
[0362] Along the thickness direction of the battery cell, the ratio of the size of the first part to the size of the end cap is within the above range, which is beneficial to increase the area of the first part, thereby increasing the solderable area of the tab and electrode terminal, reducing connection resistance, reducing heat generation, further improving the temperature distribution uniformity of the positive electrode active material layer, thereby reducing the probability of manganese ion dissolution from lithium transition metal phosphate particles, reducing the damage of manganese ions to the SEI film, reducing the consumption of active lithium ions, and improving the cycle stability of the hybrid system battery cell.
[0363] In some embodiments, the ratio of the size of the first portion to the size of the end cap is 0.50-0.80 along the thickness direction of the battery cell.
[0364] Along the thickness direction of the battery cell, the ratio of the size of the first part to the size of the end cap is within the above range, which is beneficial to further increase the area of the first part, further increase the solderable area of the tab and electrode terminal, reduce connection resistance, reduce heat generation, further improve the temperature distribution uniformity of the positive electrode active material layer, thereby reducing the probability of manganese ion dissolution of lithium transition metal phosphate particles, reducing the damage of manganese ions to the SEI film, reducing the consumption of active lithium ions, and improving the cycle stability of the hybrid system battery cell.
[0365] like Figure 2 and Figure 3 As shown, in some embodiments, the battery cell 7 may include a housing 20 and an electrode assembly 10.
[0366] In some embodiments, the outer casing 20 can be of various shapes, such as a cylinder, a cuboid, etc. The shape of the outer casing 20 can be determined according to the specific shape of the electrode assembly 10. For example, if the electrode assembly 10 is a cylindrical structure, the outer casing 20 can be a cylindrical structure. If the electrode assembly 10 is a cuboid structure, the outer casing 20 can be a cuboid structure. Optionally, the electrode assembly 10 is a cuboid structure.
[0367] The outer shell 20 can be made of various materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc. This application does not impose any special restrictions on this.
[0368] In some embodiments, the housing 20 includes a housing 21 and an end cap 22.
[0369] In some embodiments, the housing 21 has a cuboid structure.
[0370] In some embodiments, the thickness of the battery cell 7 is 15 mm to 30 mm. Figure 2 T0 shown in the figure represents the thickness of the battery cell 7.
[0371] In some embodiments, the thickness of the battery cell 7 can be selected as 15mm, 16mm, 17mm, 18mm, 19mm, 20mm, 21mm, 22mm, 23mm, 24mm, 25mm, 26mm, 27mm, 28mm, 29mm, 30mm or any value range between the two.
[0372] In some embodiments, the dimension of the battery cell 7 along the second direction F is 150 mm to 400 mm. Figure 2 W0 shown in the figure represents the dimension of the battery cell 7 along the second direction F.
[0373] In some embodiments, the dimensions of the battery cell 7 along the second direction F can be selected as 200mm, 205mm, 210mm, 215mm, 220mm, 225mm, 230mm, 235mm, 240mm, 245mm, 250mm, 255mm, 260mm, 265mm, 270mm, 275mm, 280mm, 285mm, 290mm, 295mm, 300mm, 305mm, 310mm, 315mm, 320mm, 325mm, 330mm, 335mm, 340mm, 345mm, 350mm, 355mm, 360mm, 365mm, 370mm, 375mm, 380mm, 385mm, 390mm, 395mm, 400mm, or any value range between the two.
[0374] In some embodiments, the height of the battery cell 7 is 80mm-250mm.
[0375] In some embodiments, the height of the battery cell 7 can be selected as 80mm, 85mm, 90mm, 95mm, 100mm, 105mm, 110mm, 115mm, 120mm, 125mm, 130mm, 135mm, 140mm, 145mm, 150mm, 155mm, 160mm, 165mm, 170mm, 175mm, 180mm, 185mm, 190mm, 195mm, 200mm, 205mm, 210mm, 215mm, 220mm, 225mm, 230mm, 235mm, 240mm, 245mm, 250mm, or any value between the two.
[0376] In this embodiment of the application, the first direction E is parallel to the height direction of the battery cell, and the second direction F, the first direction E, and the thickness direction X of the battery cell 7 are perpendicular to each other.
[0377] In some embodiments, the battery cell 7 includes electrode terminals, which include a first electrode terminal 31 and a second electrode terminal 32, wherein the first electrode terminal 31 is the positive terminal and the second electrode terminal 32 is the negative terminal.
[0378] In some embodiments, the first electrode terminal 31 is disposed on the housing 20, and may be disposed on the housing 21 or the end cap 22.
[0379] In some embodiments, the second electrode terminal 32 is disposed on the housing 20, and may be disposed on the housing 21 or the end cap 22.
[0380] The electrode assembly 10 can be a wound structure or a stacked structure. There can be one or more electrode assemblies 10 housed within the housing 20.
[0381] like Figure 3 As shown, in some embodiments, the electrode assembly includes tabs, which include a first tab 111 and a second tab 121, wherein the first tab 111 is a positive tab and the second tab 121 is a negative tab.
[0382] In some embodiments, the first tab 111 is directly connected to the first part of the first electrode terminal 31, and the first tab 111 and the first part of the first electrode terminal 31 can be directly connected by means of welding or the like.
[0383] In some embodiments, the second tab 121 is directly connected to the first part of the second electrode terminal 32, and the second tab 121 and the first part of the second electrode terminal 32 can be directly connected by means of welding or the like.
[0384] like Figure 4As shown, in some embodiments, the battery device may be a battery pack 2, which includes a housing 5 and one or more battery cell assemblies housed in the housing 5.
[0385] As an example, the battery cell assembly can also be housed in the housing 5 by directly fixing multiple battery cells to the housing 5.
[0386] As an example, the housing 5 includes a first housing portion 5a and a second housing portion 5b. The housing 5 has an accommodating space 5c. The first housing portion 5a and the second housing portion 5b are fastened together to form a closed space inside the housing 5 to accommodate the battery cell assembly. Here, "closed" refers to covering or closing, which can be either sealed or unsealed. The first housing portion 5a can be a top cover or a bottom plate.
[0387] As an example, the housing 5 may include a top cover, a frame, and a bottom plate. The top cover and the bottom plate are respectively connected to the frame, so that the interior of the housing 5 forms an enclosed space to accommodate the battery cell assembly.
[0388] In some embodiments, the housing 5 can be part of the vehicle's chassis structure. For example, a portion of the housing 5 can be at least a part of the vehicle's floor, or a portion of the housing 5 can be at least a part of the vehicle's crossbeams and longitudinal beams.
[0389] As an example, the battery cell assembly can be a battery module 6, which can be housed in the housing 5 by fixing the battery module 6 to the housing 5.
[0390] like Figure 5 As shown, the battery module 6 includes multiple battery cells 7.
[0391] For example, the battery module 6 includes a plurality of first battery packs 70 arranged along the length direction M of the battery module 6, and each first battery pack 70 includes a plurality of individual battery cells 7. Optionally, the battery module 6 includes four first battery packs 70 arranged along the length direction M of the battery module 6.
[0392] A second aspect of this application provides a battery device, including the battery cell provided in the first aspect of this application.
[0393] The battery device disclosed in this application can be used in electrical devices that use the battery device as a power source or in various energy storage systems that use the battery device as an energy storage element. Besides vehicles, the battery device can also be used in, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0394] A third aspect of this application provides an electrical device that uses a battery as a power source, the electrical device including at least one of the battery cell, battery module, or battery pack provided in this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The battery cell, battery module, or battery pack can be selected as the electrical device according to its usage requirements.
[0395] Figure 6 This is an example of an electrical device. The electrical device disclosed in this application can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A battery device is installed inside the vehicle, and the battery device can be located at the bottom, front, or rear of the vehicle. The battery device can be used to power the vehicle; for example, the battery device can serve as the vehicle's operating power source. The vehicle may also include a controller and a motor. The controller is used to control the battery device to supply power to the motor, for example, for the vehicle's starting, navigation, and operating power needs. In some embodiments of this application, the battery device can not only serve as the vehicle's operating power source but also as the vehicle's drive power source, replacing or partially replacing gasoline or natural gas to provide driving power for the vehicle.
[0396] The fourth aspect of this application provides an energy storage device that uses a battery device as a power source. The energy storage device can be, but is not limited to, an energy storage container, an energy storage cabinet, an energy storage power station, an energy storage battery pack, or a portable energy storage system.
[0397] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0398] I. Preparation Method 1. Preparation of Example 1 (1) Positive electrode plate ① Preparation of lithium-containing transition metal phosphate particles S1. Take 35.6 kg of manganese tetroxide, 56.1 kg of ferric phosphate, 41.6 kg of lithium dihydrogen phosphate, 15.7 kg of lithium carbonate, 0.75 kg of titanium dioxide, and 6.7 kg of glucose into a ball mill jar, add ultrapure water to form a raw slurry with a solid content of 40%. Pour the mixture into a ball mill and mix thoroughly, then transfer it to a sand mill at 800 rpm. When the slurry particle size reaches 0.51 μm, transfer it to a centrifugal spray tower for spray drying, controlling the inlet air temperature at 250℃ and the outlet air temperature at 90℃ to obtain the first spray-dried material. Sinter the spray-dried material at 550℃ under a nitrogen atmosphere for 8 hours to obtain a first-burnt sample.
[0399] S2. Take 100 kg of the above-mentioned first-burned sample, 4.8 kg of glucose, and 5.2 kg of polyethylene glycol (Polyethylene Glycol 6000) and pour them into a ball mill jar. Add ultrapure water to disperse the mixture, controlling the solid content of the slurry to 40%. Transfer the slurry to a sand mill and mill until the particle size is 0.34 μm. Then, transfer the slurry to a centrifugal spray tower for spray drying, controlling the inlet air temperature to 250℃ and the outlet air temperature to 90℃ to obtain the second spray-dried material. Sinter the second spray-dried material at 760℃ under a nitrogen atmosphere for 10 hours to obtain the second-burned sample.
[0400] S3. Place the calcined sample in an air jet mill, control the air pressure to 0.24 MPa and the grading frequency to 72 Hz to obtain air-jet material; then sieve and demagnetize the air-jet material to obtain lithium transition metal phosphate particles LMFP-1.
[0401] The lithium-containing transition metal phosphate particles comprise a particle body and carbon material disposed on at least a portion of the surface of the particle body. Based on the total mass of the lithium-containing transition metal phosphate particles, the carbon material accounts for 1.45% of the total mass. The chemical formula of the particle body of the lithium-containing transition metal phosphate particles is LiMn. 0.594 Fe 0.396 Ti 0.005 PO4.
[0402] ② Preparation of the positive electrode film Preparation of positive electrode undercoat: The conductive agent Super P and the binder polyvinylidene fluoride are mixed evenly at a total mass ratio of 55%:45%, and coated onto a 15μm positive electrode current collector aluminum foil. After drying, a positive electrode current collector coated with the positive electrode undercoat is obtained.
[0403] Preparation of positive electrode active material layer: Positive electrode active material, conductive agent, and binder polyvinylidene fluoride were mixed in a mass ratio of 96.0:2.5:1.5 in the solvent N-methylpyrrolidone. The mixture was thoroughly stirred and dispersed in a mixing tank to form a slurry for the positive electrode active material layer. After stirring, the slurry was transferred and coated onto a current collector aluminum foil, then dried, compacted, slit, and sheeted to obtain the positive electrode sheet. The one-sided density of the positive electrode active material layer was 310 mg / 1540 cm³. 2 .
[0404] The positive electrode active material includes lithium-containing transition metal oxide particles (LiNi) with a mass ratio of 7:3. 0.6 Co 0.2 Mn 0.2 O2 single crystal particles and lithium-containing transition metal phosphate particles prepared above; the conductive agent is carbon nanotubes and Super P in a mass ratio of 1:1.
[0405] When the battery cell is at 0% SOC, in the cross-section along the thickness direction of the positive electrode active material layer, the Dn10 of the lithium transition metal oxide particles is 0.95 μm, Dn50 is 2.0 μm, and Dn90 is 3.65 μm, and the compaction density of the positive electrode film is 3.0 g / cm³. 3 .
[0406] (2) Negative electrode plate A negative electrode slurry was prepared by mixing graphite (anode active material), conductive carbon black (conductive agent), styrene-butadiene rubber (SBR) (binder), and sodium carboxymethyl cellulose (CMC) (thickener) in deionized water at a mass ratio of 97:0.8:1.2:1. The slurry was then coated onto a 6 μm thick copper foil current collector, dried, compacted, slit, and sheeted to obtain the negative electrode sheet. The one-sided density of the negative electrode film was 170 mg / 1540.25 cm³. 2 .
[0407] The negative electrode active material has a Dv50 of 14 μm and a specific surface area of 1.8 m². 2 / g.
[0408] (3) Separating membrane Inorganic material boehmite, binder polyvinylidene fluoride (PVDF), acrylic emulsion, and deionized water were mixed uniformly in a mass ratio of 40%:2%:4.5%:53.5% to prepare a second coating slurry. This second coating slurry was applied to the base membrane near the positive electrode and dried. PVDF was then dissolved in water to prepare a first coating slurry, which was sprayed onto both sides of the base membrane bearing the second coating. After drying and slitting, a separator membrane was obtained. Specifically, the base membrane has both a first and second coating on the side facing the positive electrode, and a first coating on the side facing the negative electrode. The base membrane is a 7 μm thick polypropylene membrane, the first coating on one side is 0.5 μm thick, and the second coating on the positive electrode side is 3 μm thick.
[0409] (4) Electrolyte Based on the total mass of the electrolyte, the electrolyte comprises 46.85% EMC, 14% DEC, 26% EC, 0.2% lithium difluorosulfonyl imide, 3.3% lithium difluorophosphate, 7% lithium hexafluorophosphate, 0.65% 1,3-propanesulfonyl lactone, and 2% vinylene carbonate.
[0410] (5) Battery cell The positive electrode, separator, and negative electrode are stacked in sequence. The separator must be able to isolate the positive and negative electrodes. The electrode assembly is obtained by winding. The electrode assembly is placed in the housing cavity of the casing, the end cap is closed, electrolyte is injected, and after processes such as encapsulation, formation, and venting, a battery cell is obtained. The rated cutoff voltage of the battery cell is set to 4.25V.
[0411] like Figure 2 As shown, the battery cell includes a first electrode terminal and a second electrode terminal, and the electrode assembly includes a first tab and a second tab. The first tab is directly connected to the first electrode terminal, and the second tab is directly connected to the second electrode terminal. The first electrode terminal is the positive electrode terminal, the first tab is the positive tab, the second electrode terminal is the negative electrode terminal, and the second tab is the negative tab.
[0412] Along the thickness direction of the battery cell, the ratio of the size of the first part of the electrode terminal to the size of the end cap is 0.74, where the size of the first part along the thickness direction of the battery cell is specifically 14 mm, and the size of the end cap is specifically 19 mm.
[0413] 2. Preparation of other embodiments The preparation methods of Examples 2-5 and Comparative Examples 1-2 are basically the same as those of Example 1, except that the amount of manganese tetroxide and iron phosphate added in the preparation of lithium transition metal phosphate particles S1 is adjusted so that the molar ratio of manganese element is different based on the total molar number of transition metal elements in the lithium transition metal phosphate particles, as detailed in Table 1.
[0414] Examples 6-9 and Comparative Example 3 are prepared in basically the same way as Example 1, except that the fractionation frequency in the preparation of lithium transition metal phosphate particles S3 is adjusted.
[0415] The preparation method of Example 10 is basically the same as that of Example 1, except that the lithium transition metal phosphate particles include lithium transition metal phosphate LMFP-10.1 and lithium transition metal phosphate LMFP-10.2 with a mass ratio of 3:7. The preparation methods of lithium transition metal phosphates LMFP-10.1 and LMFP-10.2 are basically the same as those of lithium transition metal phosphate LMFP-1, with the difference being: when preparing LMFP-10.1, the grinding in S2 is controlled to 0.3 μm and the grading frequency in S3 is adjusted; when preparing LMFP-10.2, the grinding in S2 is controlled to 0.4 μm and the grading frequency in S3 is adjusted.
[0416] The preparation methods of Comparative Example 4 and Example 10 are basically the same, except that the lithium transition metal phosphate particles include lithium transition metal phosphate LMFP-10.1 and lithium transition metal phosphate LMFP-10.2 in a mass ratio of 2.5:7.5.
[0417] The preparation of the battery cells in Examples 11-17 is similar to that in Example 1, except that the electrolyte composition is different, as shown in Table 3.
[0418] The preparation of Examples 18-20 and Comparative Example 5 is similar to that of Example 1, except that the size of the first part or the structural design of the tabs and electrode terminals are different, as shown in Table 4.
[0419] The preparation of the battery cell in Example 21 is similar to that in Example 1, except that the composition of the conductive agent in the positive electrode is different, as shown in Table 5.
[0420] II. Testing Methods 1. Cyclic stability test At 45℃, the battery cells were charged at a constant current of 1C to 4.25V, then allowed to stand for 10 minutes. They were then charged at a constant voltage of 4.25V until the current reached 0.05C, at which point charging was stopped. After the battery cells were allowed to stand at 45℃ for 1 hour, they were discharged at 1C at 45℃ until the discharge cutoff voltage of 2.5V was reached. This constituted one cycle. The discharge capacity of each cycle was recorded, along with the number of cycles required to reduce the capacity to 80% of the initial discharge capacity.
[0421] 2. Current distribution test of lithium transition metal oxide particles and lithium transition metal phosphate particles in battery cells The areal loading of lithium transition metal oxide particles and lithium transition metal phosphate particles in a single battery cell is determined. The bifacial loading of the positive electrode of the battery cell is denoted as A, and the mass percentages of lithium transition metal oxide particles and lithium transition metal phosphate particles are denoted as a1 and a2, respectively. The bifacial loading of lithium transition metal oxide particles is calculated using the formula: areal loading = A·a1, and the bifacial loading of lithium transition metal phosphate particles is calculated using the formula: areal loading = A·a2. The lithium transition metal oxide particles and lithium transition metal phosphate particles are then combined with the negative electrode according to their respective areal loadings to prepare pouch cells. After connecting these pouch cells in parallel, the current magnitude of each pouch cell and the total positive and negative terminal voltages are collected under preset energizing conditions.
[0422] At 25℃, the total capacity of the independent cells containing lithium transition metal oxide particles and lithium transition metal phosphate particles was taken as the total capacity. The parallel cells were charged with a constant current of 2C of the total capacity to 4.35V, then left to stand for 10 minutes. Then, constant voltage charging was performed at 4.25V until the current was 0.05C of the total capacity. The charging was then stopped. The total positive and negative terminal voltages during the charging process, as well as the current flowing through the soft-pack cells containing lithium transition metal oxide particles and lithium transition metal phosphate particles, were recorded.
[0423] III. Analysis of Test Results for Each Embodiment and Comparative Example Batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in the table below.
[0424] Table 1
[0425] Table 2
[0426] Table 3
[0427] Table 4
[0428] Table 5
[0429] As can be seen from the comparison of the embodiments and comparative examples of this application, the positive electrode active material includes lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles; the lithium-containing transition metal oxide particles include nickel, cobalt, and M elements, where M elements include manganese and / or aluminum; the lithium-containing transition metal phosphate particles include iron and manganese; based on the total molar number of manganese and iron elements in the lithium-containing transition metal phosphate particles, the molar percentage of manganese is 40%-75%; in the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium-containing transition metal phosphate particles is 100nm-300nm, and the Dn90 of the lithium-containing transition metal phosphate particles is 250nm-500nm; and when the tabs on the electrode assembly are directly connected to the first part on the electrode terminal, it is beneficial to improve the cycle stability of the battery cell.
[0430] As can be seen from the comparison between Examples 2 and 5 and Examples 1, 3 and 4, when the total molar number of manganese and iron in the lithium transition metal phosphate particles is 50%-70%, it is beneficial to improve the cycle stability of the battery cell.
[0431] As can be seen from the comparison between Example 9 and Examples 1, 6, 7 and 8, when the Dn50 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet is 100nm-250nm, it is beneficial to improve the cycle stability of the battery cell.
[0432] As can be seen from the comparison between Example 10 and Example 1, when the Dn90 of the lithium transition metal phosphate particles in the cross-section of the positive electrode active material layer along the electrode thickness direction is 260nm-400nm, it is beneficial to improve the cycle stability of the battery cell.
[0433] As can be seen from the comparison between Examples 11 and 14 and Examples 1, 12 and 13, the electrolyte includes a third component, which includes vinylene carbonate. Based on the total mass of the electrolyte, when the mass percentage of the third component is 0.5%-3%, it is beneficial to improve the cycle stability of the battery cell.
[0434] As can be seen from the comparison between Example 16 and Examples 1 and 15, when the electrolyte includes a first component, and the first component includes one or more of lithium bis(fluorosulfonyl)imide and lithium difluorophosphate, it is beneficial to improve the cycle stability of the battery cell.
[0435] As can be seen from the comparison between Example 15 and Example 1, when the mass ratio of the first component is 2%-5% based on the total mass of the electrolyte, it is beneficial to improve the cycle stability of the battery cell.
[0436] As can be seen from the comparison between Example 17 and Example 1, the electrolyte includes a second component, which includes 1,3-propanesulfonyl lactone. When the mass percentage of the second component is 0.5%-1% based on the total mass of the electrolyte, it is beneficial to improve the cycle stability of the battery cell.
[0437] As can be seen from the comparison between Example 20 and Examples 1, 18 and 19, when the ratio of the size of the first part to the size of the end cap is 0.50-0.80 along the thickness direction of the battery cell, it is beneficial to improve the cycle stability of the battery cell.
[0438] As can be seen from the comparison between Example 21 and Example 1, the first conductive agent includes dot-shaped conductive agent and linear conductive agent, which is beneficial to improving the cycle stability of battery cells.
[0439] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A battery cell, characterized in that, The device includes a housing, electrode terminals, electrode assemblies, and an electrolyte. The housing forms a cavity inside and has a through hole communicating with the inside and outside of the cavity. The electrode terminals include a first part and a second part. The first part is entirely located inside the cavity, and the second part passes through the through hole and is partially located outside the cavity. The first part and the second part are integral structures. The electrode assembly and the electrolyte are disposed within the receiving cavity. The electrode assembly includes an electrode sheet and a tab, with the tab directly connected to the first part. The electrode sheet includes a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The positive active material layer includes a positive active material, which includes lithium-containing transition metal oxide particles and lithium-containing transition metal phosphate particles. The lithium-containing transition metal oxide particles include nickel, cobalt, and M elements, with the M element including manganese and / or aluminum. The lithium-containing transition metal phosphate particles include iron and manganese. Based on the total molar number of manganese and iron in the lithium-containing transition metal phosphate particles, the molar percentage of manganese is 40%-75%. In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium transition metal phosphate particles is 100nm-300nm, and the Dn90 of the lithium transition metal phosphate particles is 250nm-500nm. Here, Dn50 and Dn90 refer to the particle size corresponding to the cumulative number of particles of 50% and 90% in the cumulative distribution curve of particle number.
2. The battery cell according to claim 1, characterized in that, Based on the total number of moles of manganese and iron in the lithium-containing transition metal phosphate particles, the molar percentage of manganese is 45%-75%.
3. The battery cell according to claim 2, characterized in that, Based on the total number of moles of manganese and iron in the lithium-containing transition metal phosphate particles, the molar percentage of manganese is 50%-70%.
4. The battery cell according to any one of claims 1-3, characterized in that, The positive electrode active material satisfies one or more of the following conditions: (1) In the cross section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium transition metal phosphate particles is 100nm-250nm; (2) In the cross section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn90 of the lithium transition metal phosphate particles is 260nm-400nm; (3) In the cross section along the thickness direction of the positive electrode active material layer, the Dn10 of the lithium transition metal phosphate particles is 70nm-130nm, where Dn10 refers to the particle size corresponding to the cumulative number of particles of 10% in the cumulative distribution curve of particle number.
5. The battery cell according to claim 1, characterized in that, The electrolyte includes a first component, which includes one or more of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethanesulfonyl)imide.
6. The battery cell according to claim 5, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the first component is 0.05%-7%.
7. The battery cell according to claim 6, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the first component is 0.5%-5%.
8. The battery cell according to claim 7, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the first component is 2%-5%.
9. The battery cell according to any one of claims 5-8, characterized in that, The first component includes one or more of lithium bis(fluorosulfonyl)imide and lithium difluorophosphate.
10. The battery cell according to claim 9, characterized in that, Based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 0.05%-2%; Alternatively, based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate is 1%-5%.
11. The battery cell according to claim 10, characterized in that, Based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 0.1%-2%.
12. The battery cell according to claim 10, characterized in that, Based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate is 2%-5%.
13. The battery cell according to claim 1, characterized in that, The electrolyte includes lithium hexafluorophosphate, and the mass percentage of lithium hexafluorophosphate is 5%-12% based on the total mass of the electrolyte.
14. The battery cell according to claim 1, characterized in that, The electrolyte includes a second component, which includes one or more of 1,3-propanesulfonyl lactone, lithium difluorooxalate borate, trimethylsilyl phosphate, lithium dioxalate borate, and vinyl sulfate.
15. The battery cell according to claim 14, characterized in that, The second component includes 1,3-propanesulfonyl lactone.
16. The battery cell according to claim 14 or 15, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the second component is 0.2%-5%.
17. The battery cell according to claim 16, characterized in that, Based on the total mass of the electrolyte, the second component accounts for 0.5%-3% of the total mass.
18. The battery cell according to claim 17, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the second component is 0.5%-1%.
19. The battery cell according to claim 1, characterized in that, The electrolyte comprises cyclic carbonate compounds, and the cyclic carbonate compounds account for 20%-45% of the total mass of the electrolyte.
20. The battery cell according to claim 19, characterized in that, Based on the total mass of the electrolyte, the cyclic carbonate compound accounts for 18%-35% of the total mass.
21. The battery cell according to claim 19 or 20, characterized in that, The cyclic carbonate compounds include one or more of ethylene carbonate, propylene carbonate, and butene carbonate.
22. The battery cell according to claim 21, characterized in that, The cyclic carbonate compounds include ethylene carbonate.
23. The battery cell according to claim 1, characterized in that, The electrolyte comprises chain carbonate compounds, and the chain carbonate compounds account for 40%-75% of the total mass of the electrolyte.
24. The battery cell according to claim 23, characterized in that, Based on the total mass of the electrolyte, the chain carbonate compound accounts for 50%-70% of the mass.
25. The battery cell according to claim 23 or 24, characterized in that, The chain carbonate compounds include one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methyl propyl carbonate.
26. The battery cell according to claim 25, characterized in that, The chain carbonates include methyl ethyl carbonate and diethyl carbonate.
27. The battery cell according to claim 25, characterized in that, The electrolyte includes ethyl methyl carbonate, and the ethyl methyl carbonate accounts for 35%-55% of the total mass of the electrolyte. And / or, the electrolyte includes diethyl carbonate, and the mass percentage of diethyl carbonate is 10%-20% based on the total mass of the electrolyte.
28. The battery cell according to claim 1, characterized in that, The electrolyte includes a third component, which includes one or more of vinylene carbonate and fluoroethylene carbonate.
29. The battery cell according to claim 28, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the third component is 0.08%-5%.
30. The battery cell according to claim 29, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the third component is 0.5%-3%.
31. The battery cell according to claim 1, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium-containing transition metal oxide particles is 1μm-4μm.
32. The battery cell according to claim 31, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium-containing transition metal oxide particles is 1μm-3μm.
33. The battery cell according to claim 32, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn50 of the lithium-containing transition metal oxide particles is 1.5μm-2.5μm.
34. The battery cell according to claim 1, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the particle size distribution concentration of the lithium-containing transition metal oxide particles (Dn90-Dn10) / Dn50 is 0.6-2.
35. The battery cell according to claim 34, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the particle size distribution concentration of the lithium-containing transition metal oxide particles (Dn90-Dn10) / Dn50 is 0.8-1.
8.
36. The battery cell according to claim 1, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn10 of the lithium-containing transition metal oxide particles is 0.5μm-2μm; And / or, in the cross-section of the positive electrode active material layer along the electrode thickness direction, the Dn90 of the lithium-containing transition metal oxide particles is 3μm-4μm.
37. The battery cell according to claim 36, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn10 of the lithium-containing transition metal oxide particles is 0.5μm-1.5μm.
38. The battery cell according to claim 36, characterized in that, In the cross-section of the positive electrode active material layer along the thickness direction of the electrode sheet, the Dn90 of the lithium-containing transition metal oxide particles is 3μm-4μm.
39. The battery cell according to claim 1, characterized in that, Based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles, the molar percentage of nickel is 50%-80%.
40. The battery cell according to claim 1, characterized in that, Based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles, the molar percentage of cobalt is 5%-20%.
41. The battery cell according to claim 1, characterized in that, Based on the total molar number of nickel, cobalt and M elements in the lithium-containing transition metal oxide particles, the molar percentage of M element is 15%-40%.
42. The battery cell according to claim 1, characterized in that, The lithium-containing transition metal oxide particles are single-crystal particles.
43. The battery cell according to claim 1, characterized in that, Based on the total mass of the positive electrode active material, the mass percentage of the lithium-containing transition metal oxide particles is 50%-90%.
44. The battery cell according to claim 43, characterized in that, Based on the total mass of the positive electrode active material, the mass percentage of the lithium-containing transition metal oxide particles is 60%-80%.
45. The battery cell according to claim 1, characterized in that, The lithium-containing transition metal oxide particles include one or more of lithium-containing nickel-cobalt-manganese oxides and their doped and / or coated modified materials, and lithium-containing nickel-cobalt-aluminum oxides and their doped and / or coated modified materials.
46. The battery cell according to claim 1, characterized in that, The lithium-containing transition metal phosphate particles include a particle body and a carbon material disposed on at least a portion of the surface of the particle body.
47. The battery cell according to claim 46, characterized in that, The thickness of the carbon material is 2nm-25nm; And / or, based on the total mass of the lithium transition metal phosphate particles, the carbon material accounts for 0.5%-3% of the total mass.
48. The battery cell according to claim 1, characterized in that, The lithium-containing transition metal phosphate particles comprise the components represented by the following general formula I: Li m1 Fe x1 Mn y1 M1 b1 P z1 Q1 c1 O n1 N1 d1 Formula I; Wherein, 0.8≤m1≤1.2, 0<x1<1, 0<y1<1, 0.9≤x1+y1≤1, 0.95≤z1≤1, 3.5≤n1≤4, 0≤b1≤0.1, 0≤c1≤0.1, 0≤d1≤0.1; wherein, M1 includes one or more of Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, and Ti, Q1 includes one or more of B, S, Si, and N, and N1 includes one or more of F, Cl, and Br.
49. The battery cell according to claim 1, characterized in that, The positive electrode active material layer includes a first conductive agent, which includes a dotted conductive agent, and the dotted conductive agent includes one or more of Super P, Ketjen Black, acetylene black, and conductive graphite.
50. The battery cell according to claim 49, characterized in that, Based on the total mass of the positive electrode active material layer, the mass percentage of the dotted conductive agent is 0.2%-2.0%.
51. The battery cell according to claim 49 or 50, characterized in that, The first conductive agent further includes a linear conductive agent, which includes one or more of carbon nanotubes, vapor-grown carbon fibers, and carbon nanofibers.
52. The battery cell according to claim 51, characterized in that, The first conductive agent includes carbon nanotubes.
53. The battery cell according to claim 51, characterized in that, Based on the total mass of the positive electrode active material layer, the mass percentage of the linear conductive agent is 0.05%-1.5%.
54. The battery cell according to claim 53, characterized in that, Based on the total mass of the positive electrode active material layer, the mass percentage of the linear conductive agent is 0.05%-1.25%.
55. The battery cell according to claim 1, characterized in that, The positive electrode includes a positive electrode film layer disposed on at least one side of the positive electrode current collector. The positive electrode film layer includes the positive electrode active material layer and a positive electrode undercoating layer disposed between the positive electrode active material layer and the positive electrode current collector. The positive electrode undercoating layer includes a first polymer and a second conductive agent.
56. The battery cell according to claim 55, characterized in that, The thickness of the positive electrode undercoat is 0.5μm-5μm.
57. The battery cell according to claim 55 or 56, characterized in that, The compaction density of the positive electrode film is 2.60 g / cm³. 3 -3.4g / cm 3 .
58. The battery cell according to claim 1, characterized in that, The electrode assembly includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, which includes graphite, and the volume distribution particle size Dv50 of the negative electrode active material is 7μm-15μm.
59. The battery cell according to claim 58, characterized in that, The volume distribution particle size Dv50 of the negative electrode active material is 8μm-13μm.
60. The battery cell according to claim 1, characterized in that, The electrode assembly further includes a separator disposed on at least one side of the positive electrode sheet. The separator includes a base film, a first coating disposed on both sides of the base film, and a second coating disposed between the first coating and the base film. The first coating includes a second polymer, and the second coating includes inorganic particles and a third polymer.
61. The battery cell according to claim 60, characterized in that, The second coating is applied to the side close to the positive electrode sheet.
62. The battery cell according to claim 60, characterized in that, The second polymer and the third polymer each independently include one or more of fluoropolymers and acrylate polymers.
63. The battery cell according to claim 62, characterized in that, The fluoropolymer includes vinylidene fluoride polymers, which include one or more of the following: vinylidene fluoride homopolymers, copolymers of vinylidene fluoride and tetrafluoroethylene, copolymers of vinylidene fluoride and hexafluoropropylene, and copolymers of vinylidene fluoride and trifluoroethylene; and / or, The acrylate polymers include acrylate-acrylonitrile-acrylamide-propylene copolymers.
64. The battery cell according to claim 60, characterized in that, The inorganic particles include one or more of alumina, boehmite, silicon dioxide, cerium oxide, magnesium aluminate, zirconium oxide, and titanium dioxide.
65. The battery cell according to claim 1, characterized in that, The rated cutoff voltage of the battery cell is 4.25V-4.45V.
66. The battery cell according to claim 1, characterized in that, The housing also includes an end cap, and the ratio of the size of the first portion to the size of the end cap is 0.35-0.80 along the thickness direction of the battery cell.
67. The battery cell according to claim 66, characterized in that, The ratio of the size of the first part to the size of the end cap is 0.50-0.
80.
68. A battery device, characterized in that, Includes the battery cell according to any one of claims 1-67.
69. An electrical appliance, characterized in that, Includes the battery device of claim 68, the battery device being used to provide electrical energy.
70. An energy storage device, characterized in that, Includes the battery device of claim 68, the battery device being used for storing electrical energy.
Citation Information
Patent Citations
Secondary battery and electric device
CN119852484A
Secondary battery and electric device
CN119852485A